Method for recovering lithium and other metals from waste ion batteries

JP7645862B2Active Publication Date: 2025-03-14BASF SE
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022504525
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-14
Filing Date
2020-07-24
Publication Date
2025-03-14
Estimated Expiration
2040-07-24

Smart Images

  • Figure 0007645862000012
    Figure 0007645862000012
  • Figure 0007645862000013
    Figure 0007645862000013
  • Figure 0007645862000014
    Figure 0007645862000014
Patent Text Reader

Abstract

A method for recovering one or more transition metals and lithium from waste lithium-ion batteries or parts thereof is disclosed. The method includes the steps of: (a) preparing a particulate material containing a transition metal compound and / or a transition metal, where the transition metal is selected from the group consisting of Ni and Co, and further, if present, at least a portion of the Ni and / or Co is in an oxidation state lower than +2, e.g., metallic, and the particulate material further contains a lithium salt; (b) treating the material prepared in step (a) with a polar solvent and, optionally, an alkaline earth hydroxide; (c) separating the solid from the liquid, optionally followed by solid-solid separation; and (d) treating the transition metal-containing solid, typically with a mineral acid, to dissolve at least a portion of the Ni and / or Co. This method successfully separates high-purity lithium and the transition metal useful for producing active battery cathode materials.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention is directed to a method for recovering lithium and other metals from spent lithium-ion batteries or production waste containing at least one of the transition metals nickel, manganese and cobalt, particularly involving the extraction of lithium as lithium hydroxide from particulate material obtained from lithium-ion batteries, particularly cell materials thereof, typically after discharge, crushing and reduction at high temperatures, and separating the lithium from undesirable impurities in a refining process by recovering other metals, such as nickel, manganese and / or cobalt, from the residue after the extraction step. [Background technology]

[0002] The storage of electrical energy is a subject of growing interest. Efficient storage of electrical energy allows for the generation of electrical energy when and where it is needed. Secondary lithium batteries are of particular interest for energy storage because, due to the small atomic weight and large ionization energy of lithium, they offer high energy density and have become widely used as power sources for many portable electronic devices, such as mobile phones, laptop computers, mini cameras, etc., as well as for electric vehicles. In particular, the increasing demand for raw materials, such as lithium, cobalt, and nickel, will pose challenges in the future.

[0003] The lifespan of lithium-ion batteries is not unlimited. Therefore, it is expected that an increasing number of used lithium-ion batteries will be generated. Because lithium-ion batteries contain important transition metals, such as, but not limited to, cobalt and nickel, as well as lithium, used lithium-ion batteries may form a valuable source of raw materials for the new manufacture of lithium-ion batteries. For this reason, an increasing number of research activities are being carried out with the goal of recycling transition metals and lithium from used lithium-ion batteries or from batteries or their parts that do not meet specifications and requirements (such off-specification materials and production waste may also be a source of raw materials).

[0004] Two main processes are targeted for raw material recovery. One is the direct hydrometallurgical processing of battery scrap materials. The principle is disclosed in WO 2017 / 091562 and J. Power Sources, 2014, 262, 255 ff. Such hydrometallurgical processes provide transition metals in aqueous solutions, e.g., sulfate solutions, or in precipitated form, e.g., hydroxides, either separately or already with the desired stoichiometries for producing new cathode active materials. In the latter case, the composition of the metal salt solution may be adjusted to the desired stoichiometry by adding single metal components.

[0005] WO 2017 / 091562 describes the co-precipitation of transition metals, and WO 2014 / 180743 describes a co-precipitation process using ammonia or amines.

[0006] Typically, batteries are first disassembled into modules or even cells. In direct hydrometallurgical processes, battery scrap is mechanically processed to separate large parts from the casing and wiring. The electrode active material, i.e., graphite in the case of the anode and lithium transition metal oxide in the case of the cathode, together with some impurities, forms a fine powder, so-called black mass or black powder, that constitutes the feed for subsequent hydrometallurgical process steps. In some processes, battery scrap is subjected to a heat treatment or pyrolysis step carried out at a temperature well below the melting point of the transition metals contained in the scrap, in this respect differing from refining processes that operate at temperatures above the melting point of the transition metals contained in the scrap.

[0007] Such heat-treated black mass can be obtained from the treatment of batteries in a waste incineration oven. Waste batteries, or battery modules or cells, are fed to the incineration oven, where the battery feed is partially combusted. The product of this treatment is cooled and mechanically treated using any type of crushing or grinding equipment suitable for separating the metal fraction from the powdery black mass. These black masses are, under normal conditions, low-reactivity materials and can therefore be easily transported.

[0008] Several authors have described the thermal treatment of waste lithium-ion batteries or components containing the electrode active materials of these types of batteries at temperatures above 400 °C. This thermal treatment completely evaporates the electrolyte solvent contained in the battery and decomposes the polymer components. The material resulting from this thermal treatment may be subjected to different mechanical treatments and separation operations to separate different metal fractions and powder materials, primarily comprising the electrode active materials from the anode, i.e., graphite, and the electrode active materials from the cathode, i.e., lithium-containing transition metal materials. These powders are often referred to as "black masses" or "black powders," or "active masses." Depending on the reaction conditions, the latter materials are often at least partially reduced, thereby containing metallic Ni and Co phases, manganese oxide phases, and lithium salts such as LiOH, Li2CO3, LiF, LiAlO2, and Li3PO4. Reduction occurs either through the introduction of reducing gases such as hydrogen or carbon monoxide under reducing conditions during heat treatment, or, at temperatures above 500°C, through the carbonaceous materials contained in the waste battery material, i.e., graphite and soot. J. Li et al., J. Hazard. Mat. 2016, 302, 97 ff., discloses an oxygen-free roasting / wet magnetic separation process for the recovery of cobalt, lithium carbonate, and graphite from spent LiCoO2 / graphite batteries.

[0009] In JP 2012-229481 A, waste batteries are processed in multiple steps to bind the fluorine contained in the batteries in a conductive electrolyte salt, usually LiPF6, and a binder polymer, usually polyvinylidene fluoride (PVDF). This is achieved by first treating the waste batteries with an aqueous calcium hydroxide (slaked lime) solution to hydrolyze the conductive salt and precipitate the fluoride as calcium fluoride. Starting with conversion experiments using model materials such as LiCoO2, JP 2012-229481 A discloses a method for recovering metals from used lithium-ion batteries, including a pre-soaking step, followed by aqueous treatment with high-temperature oxidation, reduction roasting, and filtration, as well as recovery of lithium carbonate from the filtrate and transition metals from the residue.

[0010] The other main method is based on the direct smelting of the corresponding battery scrap (e.g., EP 1 589 121 A1). This results in a metal alloy containing Ni and Co, while lithium is lost in the slag, from which it is very difficult to recover. The obtained metal alloy can be processed by hydrometallurgy to extract metals, such as transition metals. JP 2012-112027 A describes the separation of lithium and cobalt by evaporation from the melt, and therefore such a method is envisaged to operate above the boiling temperature of cobalt (i.e., above 2870°C). [Prior art documents] [Patent documents]

[0011] [Patent Document 1] International Publication No. 2017 / 091562 [Patent Document 2] International Publication No. 2014 / 180743 [Patent Document 3] Japanese Patent Application Laid-Open No. 2012-229481 [Patent Document 4] European Patent Application Publication No. 1589121 [Patent Document 5] Japanese Patent Application Laid-Open No. 2012-112027 [Non-patent literature]

[0012] [Non-Patent Document 1] J. Power Sources, 2014, 262, 255 ff. [Non-patent document 2] J. Li et al., J. Hazard. Mat. 2016, 302, 97 ff Summary of the Invention [Problem to be solved by the invention]

[0013] Known methods for recovering valuable materials typically face the problem that used batteries, i.e., the cells containing the majority of these materials, contain high levels of impurities, such as fluorine and / or phosphorus compounds, which must be removed in order to recover the desired materials (battery-grade materials) at a purity that can be used in the production of new cells. Therefore, it is an object of the present invention to provide a method that can easily recover the valuable metals contained in battery scrap, i.e., lithium, nickel, and, if present, cobalt and manganese. It is another object of the present invention to provide a method for recovering additional elements, such as carbon as graphite and fluorides. It is a further object of the present invention to provide an economical method that reduces the number of expensive and / or energy-consuming steps. It is a further object of the present invention to provide a method for recovering the transition metals or their compounds at high purity, particularly with low contents of copper and precious metals such as Ag, Au, and platinum-group metals, and high-purity lithium or its compounds with low contents of fluorine and / or phosphorus or other metallic impurities. Typically, the recovered metals or metal compounds are converted to the corresponding transition metal salts, often sulfates, and lithium carbonate and often lithium hydroxide.

[0014] Known methods for binding fluoride are typically complex and require multiple process steps. Therefore, it is an object of the present invention to solve the above-mentioned problems related to the recovery of Ni, Co, and lithium hydroxide from at least partially reduced black masses containing Ni and / or Co, where at least 10% of the Ni and / or Co is in an oxidation state lower than +2, e.g., metallic state, and also containing lithium salts. Such black masses are often ferromagnetic. [Means for solving the problem]

[0015] Thus, a method as defined at the outset has been found, hereinafter also referred to as the method of the invention or the recycling method of the invention, which comprises the steps defined in more detail below, hereinafter also referred to as step (a), step (b), step (c), step (d), etc.

[0016] The present invention therefore primarily relates to a method for recovering one or more transition metals and lithium as Li salts from materials comprising waste lithium-ion batteries or parts thereof, comprising: (a) providing a particulate material obtained from a lithium ion battery or part thereof, the particulate material containing a transition metal compound and / or transition metal selected from the group consisting of Ni and Co, wherein at least a portion of the Ni and / or Co is in an oxidation state lower than +2, and the particulate material further containing a lithium salt; (b) treating the material provided in step (a) with an alkaline earth hydroxide and a polar solvent, typically an aqueous solvent; (c) separating the solid containing one or more transition metals from the liquid, optionally followed by solid-solid separation to recover the transition metal, e.g., Ni; and (d) treating the solid, optionally a transition metal concentrate from solid-solid separation, containing a majority of one or more transition metals, so as to dissolve at least a portion of the nickel and / or cobalt. This relates to a method, including [Brief explanation of the drawings]

[0017] [Figure 1] FIG. 2 is an X-ray powder diffraction pattern (Mo Ka) of the reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1 and used in Example 2a, including reference diffractograms of graphite, cobalt, manganese-II oxide, cobalt oxide, and nickel. [Figure 2] 2 is an X-ray powder diffraction pattern (Mo Ka) of the reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1 and used in Example 2a, including reference diffraction patterns of graphite, lithium aluminate, and lithium carbonate. [Figure 3] 2 is an X-ray powder diffraction pattern (Cu Ka) of the reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1 and used in Example 2a, including reference diffraction patterns of graphite, cobalt, manganese-II oxide, cobalt oxide, and nickel. [Figure 4] 2 is an X-ray powder diffraction pattern (Cu Ka) of the reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1 and used in Example 2a, including reference diffraction patterns of graphite, lithium aluminate, and lithium carbonate. [Figure 5] 1 is an X-ray powder diffraction pattern (Cu Ka) of LiOH monohydrate obtained in Example 5. DETAILED DESCRIPTION OF THE INVENTION

[0018] The particulate material prepared in step (a) is obtained from a lithium-containing transition metal oxide material, which may originate from lithium-ion batteries (battery waste), including used batteries, waste battery materials from production and off-specification materials, which typically contain fluorine compounds and / or phosphorus compounds as impurities, as well as further materials containing lithium and the transition metals free of such impurities, such as cathode active materials from production waste, as described in more detail below for preliminary step (i). Prior to this step (a), the material is subjected to a reduction step, for example using a reducing gas, such as CO or hydrogen, to convert the transition metals Ni and / or Co to an oxidation state lower than +2 or to the metallic state, for example by heating the material to a temperature in the range of 200-900°C in the presence of, for example, H2.

[0019] As mentioned above, the solid residue separated in step (c) may be further subjected to solid-solid separation to recover the transition metal, for example Ni, before carrying out this step (d).

[0020] The solid-liquid separation of step (c) may be followed by an optional solid-solid separation, or the slurry obtained from step (b) may be subjected to solid-solid separation and the resulting fraction subsequently subjected to solid-liquid separation. The optional solid-solid separation (described in more detail further below as step d1) produces a solid residue enriched in transition metals, in particular nickel and / or cobalt, and a second solid residue depleted in transition metals. This method offers the advantage of preserving the lithium salts in a form that allows their recovery from solution, thus providing good recovery of lithium and transition metals.

[0021] The polar solvent used in step (b) of the present process leaches lithium salts from the material prepared in step (a), thereby providing the desired separation of lithium in a liquid phase from the transition metal remaining in the solid residue. The polar solvent is typically selected from water, alcohols, ketones, esters, organic carbonates, polyethers, nitriles, and mixtures thereof. Polar solvents that can at least partially dissolve alkaline earth hydroxides, such as calcium hydroxide, as well as, or even better than, water are particularly preferred. Examples of such solvents are polyols, such as glycols, glycerol, or polyethylene glycol, and mixtures thereof.

[0022] To improve the results of the leaching with respect to the recovery of lithium hydroxide, an alkaline earth hydroxide or alkaline earth oxide is added to the slurry, and in the case of an alkaline earth oxide, such as calcium oxide, the polar solvent used in step (b) is advantageously a protic solvent which forms the alkaline earth hydroxide in situ, such as water.

[0023] In a method of particular technical importance, the leaching liquid used in step (b) to treat the particulate material (PM) prepared in step (a) contains an alkaline earth hydroxide (AEH), such as calcium hydroxide. The addition of alkaline earth hydroxide in this step has the advantage of binding fluoride and other anions capable of forming less soluble lithium salts, such as carbonates, phosphates and aluminates.

[0024] Therefore, the present invention preferably provides a method for recovering one or more transition metals and lithium as Li salts from materials comprising waste lithium-ion batteries or parts thereof, comprising the steps of: (a) providing a particulate material obtained from waste lithium ion batteries or parts thereof, the particulate material containing a transition metal compound and / or a transition metal selected from the group consisting of Ni and Co, wherein at least a portion of the Ni and / or Co is in an oxidation state lower than +2, and the particulate material further containing a lithium salt; (b) treating the material provided in step (a) with a polar solvent, typically an aqueous solvent, and an alkaline earth hydroxide; (c) separating the solid containing one or more transition metals from the liquid, optionally followed by solid-solid separation to recover the transition metal, e.g., Ni; and (d) treating the solid containing one or more transition metals, optionally a transition metal concentrate from solid-solid separation, containing the majority of the transition metals, so as to dissolve at least a portion of the nickel and / or cobalt. This relates to a method, including

[0025] The PM preferably contains nickel and optionally a further transition metal, such as Co.

[0026] Protic solvents are primarily water, alcohols, and mixtures thereof, as described in more detail below. An aqueous medium, e.g., an aqueous solvent or liquid, contains primarily (i.e., 50% by weight (% bw) or more, particularly 80% by weight or more, more particularly 90% by weight or more) water, including water and mixtures of water with one or more alcohols, and may contain additional dissolved substances, so long as the critical water content is maintained within one or more of the ranges given above.

[0027] Step (b) primarily involves providing a suspension of particulate material in a polar solvent, preferably with heating; treatment with alkaline earth hydroxide is typically carried out at temperatures in the range of 60-200°C, preferably 70-150°C. Above the boiling point of the polar solvent, treatment is carried out in the liquid state under pressure, at which the solvent, or at least a portion of it, is maintained. The temperature range around the boiling point of water, i.e., about 70-150°C, is of particular technical importance; in this case, treatment can be achieved using aqueous liquids or water at atmospheric pressure or slightly elevated pressures (e.g., up to 5 bar). Alternatively, step (b) can be carried out by applying higher temperatures and pressures, e.g., 150-300°C and 1.5-100 bar.

[0028] Treatment is typically carried out by combining an amount of alkaline earth hydroxide (AEH) with the particulate material (PM) to correspond to at least 5%, typically no more than 100%, of the PM by weight, e.g., 50-1000 g AEH per kg PM, preferably 100-1000 g AEH, and more preferably 200-1000 g AEH per kg PM. The amount of polar solvent is typically selected to ensure miscibility of the components, e.g., 0.5-95, preferably about 2.5-21, or in certain cases 1-20, e.g., about 2-10, parts by weight of polar solvent per part by weight of combined solids (PM and AEH).

[0029] In one embodiment of the present invention, step (b) is carried out in a container protected against strong bases, such as molybdenum- and copper-rich steel alloys, nickel-based alloys, duplex stainless steel, or glass-lined or enamel- or titanium-coated steel. Further examples are polymer liners and containers made of base-resistant polymers, such as polyethylene, e.g., HDPE and UHMPE, fluorinated polyethylene, perfluoroalkoxyalkane ("PFA"), polytetrafluoroethylene ("PTFE"), PVdF, and FEP. FEP stands for fluorinated ethylene propylene polymer, i.e., a copolymer of tetrafluoroethylene and hexafluoropropylene.

[0030] The treatment is typically carried out using a mixing device, such as a stirrer, typically applying a power of up to 10 W per kg of suspension, for example 0.5-10 W / kg, and / or circulating with a pump, in order to achieve good mixing and avoid settling of insoluble components. Shearing can be further improved by utilizing baffles. Furthermore, the slurry obtained in step (b) may advantageously be subjected to a grinding treatment, for example in a ball mill or stirred ball mill, which can provide better access of the polar solvent to the finely divided lithium-containing transition metal oxide material. The applied shearing and grinding device is typically sufficiently corrosion-resistant and can be produced from the same materials and coatings as those described above for the container.

[0031] In one embodiment of the present invention, step (b) has a duration in the range of 20 minutes to 24 hours, preferably 1 to 10 hours.

[0032] In one embodiment, step (b) is carried out at least twice, with a solid-liquid separation between each run, until optimal recovery of lithium hydroxide or lithium salt is reached. The resulting lithium salt solutions may be combined or processed separately to recover the solid lithium salt.

[0033] In one embodiment of the invention, steps (b) and (c) are carried out in batch mode. In one embodiment of the invention, steps (b) and (c) are carried out in continuous mode, for example in a cascade of stirred vessels (step b) and / or in a cascade of stirred vessels plus a centrifuge (step c).

[0034] In one embodiment of the present invention, the polar solvent in step (b) is an aqueous medium, and the weight ratio of the aqueous medium to the material prepared in step (a) is within the range of 1:1 to 99:1, preferably 5:1 to 20:1.

[0035] The alkaline earth hydroxide is generally selected from hydroxides of Mg, Ca, Sr and Ba, with calcium hydroxide, barium hydroxide and mixtures thereof being preferred, and calcium hydroxide being most preferred. The alkaline earth hydroxide used in step (b) may be used as it is, or may be added in the form of an oxide or a mixture of oxide and hydroxide which forms the alkaline earth hydroxide when contacted with a polar solvent selected from the protic solvents mentioned above.

[0036] The particulate material provided in step (a) typically comprises a lithium-containing transition metal oxide material, such as material obtained from lithium-ion battery waste after a preliminary step (i) of heating under inert or reducing conditions to a temperature in the range of 80-900°C, e.g., 200-850°C, especially 200-800°C. As explained in more detail below, preliminary step (i) is typically carried out immediately after discharging, dismantling and / or crushing the lithium-ion batteries. In some applications, crushing and / or dismantling is carried out after preliminary step (i). The lithium-ion batteries used, and thus the particulate material provided in step (a), typically contain carbon, e.g., in the form of graphite.

[0037] For example, when an elevated temperature is mentioned for the treatment of a material in this step (i), the exposure time, if indicated, defines the total dwell time (synonymous with residence time) in a reactor or furnace heated to the elevated temperature, during which the temperature of the material should reach a temperature in the given range for at least a fraction of that residence time.

[0038] Unless otherwise specified, "containing" with respect to any substance generally means that such substance is present in an amount that is still detectable, typically by x-ray powder diffraction, e.g., 1% by weight or more, or that such constituents are present in an amount that is detectable, typically by ICP after suitable digestion, e.g., 10 ppm by weight or more. The particulate material provided in this step (a) typically contains, by element, about 1-10% lithium, about 3-30% a combination of transition metal elements, cobalt and / or nickel, and about 4-40% of all transition metal elements, including any cobalt, nickel, manganese, copper, and iron (all by weight percentage of the dry particulate material provided in step (a)).

[0039] In the following, the particulate material provided in step (a) and the material subjected to step (i) are alternatively collectively referred to as lithium-containing transition metal oxide material.

[0040] A carbon-containing material can be used as a reducing agent in the pretreatment for the reduction. Other reducing agents useful for providing a reducing gas stream for this preliminary step (i) are as described in JP 2012-229481 A, with hydrogen and / or carbon monoxide being preferred. Accordingly, the present invention includes a method comprising the above-described steps (i) and (a), (b), (c), and (d), wherein the heating step (i) is carried out under reducing conditions comprising the presence of carbon and / or a reducing gas selected from hydrogen, methane, and carbon monoxide.

[0041] Step (i) Method 1 When hydrogen is used as the reducing gas, the preliminary step (i) is preferably carried out as follows: (i) heating the lithium-containing transition metal oxide material in the presence of H to a temperature in the range of 200 to 900°C, or as indicated above.

[0042] Typically, the lithium-containing transition metal oxide material heated in step (i) originates from a lithium ion battery and may contain fluorine typically in the range of 1% by weight to 8% by weight and / or phosphorus in the range of 0.2% by weight to 2% by weight, relative to the weight of the lithium-containing transition metal oxide material.

[0043] Step (i), which is carried out using hydrogen, involves heating the lithium-containing transition metal oxide material to a temperature in the range of 200 to 900°C, preferably 300 to 600°C, and more preferably 350 to 500°C. It is generally preferable not to expose the lithium-containing transition metal oxide material to temperatures above 500°C, since strong heating tends to increase the formation of insoluble species (e.g., LiMnO), especially under oxidizing conditions and, to a lesser extent, under reducing atmospheres. Consequently, it is preferable to keep the temperature in step (i) below 500°C. In one embodiment of the method, step (i) is carried out using hydrogen at a temperature in the range of 350 to 450°C, e.g., 380 to 450°C, especially 380 to 440°C. The atmosphere used to carry out the reduction, according to this embodiment, contains 0.1% to 100% by volume of hydrogen, with the remainder being a non-oxidizing gas, preferably nitrogen, argon, water vapor, carbon monoxide, carbon dioxide, or a mixture of at least two of these gases. Preferred non-oxidizing gases are nitrogen and water vapor, and mixtures of nitrogen and water vapor. In a preferred embodiment, step (i) of the present process is carried out under an atmosphere mainly composed of hydrogen, for example, containing 35 to 100% by volume, preferably 50 to 100% by volume (normal conditions) of hydrogen, with the remainder, if any, being a non-oxidizing gas. In this embodiment of the present invention, step (i) has a duration (residence time) in the range of 10 minutes to 30 hours, preferably 20 minutes to 8 hours, more preferably 30 minutes to 4 hours. The duration of step (i), preferably in the presence of hydrogen, lasting 20 to 90 minutes, is of particular technical interest.

[0044] The concentration of hydrogen in the reducing atmosphere and the reaction time are interdependent: typically, lower concentrations of hydrogen require longer reduction times and vice versa.

[0045] Thus, in a preferred method of the present invention, step (i) is carried out by heating the lithium-containing transition metal oxide material to a temperature in the range of 350-450°C in the presence of more than 35 vol%, particularly 50-100 vol%, of H for a period of 20-90 minutes. A particularly preferred method within the present invention involves carrying out step (i) at a temperature between 400°C and 450°C, e.g., between 400°C and 420°C, for a maximum of 2.5 hours using 35 vol% or more of hydrogen, in order to recover Li in a particularly efficient manner in step (b). However, applying a too high temperature may result in a low yield, and a long duration tends to reduce the space-time yield, although this does not have any negative effects. A H concentration of 35 vol% or more is preferred, as it leads to a short reaction time of 2.5 hours or less, and an optimal space-time yield can be achieved using more than 80 vol% of hydrogen.

[0046] After the heat treatment, the material is transferred from the oven to a cooling unit. Here, the material is cooled, preferably to a temperature below 100°C. Cooling can be carried out under ambient conditions, for example, by storing the hot material in a chamber or container, or in a rotary tube, which may be the last unheated or cooled part of a rotary kiln where the heat treatment is carried out and heat can be transferred to the environment. Preferably, the hot material can be cooled and conveyed by a cooling conveying screw. More rapid cooling can be achieved by introducing a gas, which can be fed to a heat exchanger after passing through the hot material bed. Such gas cooling can be designed as a fixed bed, a moving bed, or a fluidized bed. The gas used is preferably an inert gas such as nitrogen, argon, or carbon dioxide. Preferably, a reducing gas can be used at the beginning of the cooling period, when the material is still at a temperature close to the oven temperature, for reduction. Subsequently, at lower temperatures, the gas composition can be changed to an inert gas, or even an oxygen-containing gas such as air, or a mixture of air and an inert gas.

[0047] Alternatively, the hot material can be quenched with a liquid to cool it under dry conditions in a gas atmosphere. Quenching can be done by spraying a cooling liquid onto the hot material, either in an amount such that the liquid evaporates and the material remains essentially dry (evaporative cooling), or in a larger amount such that a slurry of the material is formed. Liquid cooling is particularly preferred when the resulting cooled material or slurry can be used directly in step (b) of this invention. Thus, preferred quench liquids are sufficiently temperature-stable polar solvents, with water being most preferred. The liquid can be pumped through a heat exchanger and returned to the cooling vessel for recycling.

[0048] Step (i) Method 2 When a carbon-based material, such as carbon, is used as the reducing agent, the preliminary step (i) is preferably carried out as follows: (i) heating the lithium-containing transition metal oxide material in the presence of the carbon-based material, such as carbon, for example, in the presence of graphite, to a temperature in the range of 200 to 900° C. In a preferred embodiment of the present invention, graphite contained in the black mass is used as the reducing agent.

[0049] As explained in more detail below, typically the lithium-containing transition metal oxide material heated in step (i) originates from a lithium ion battery and may contain typical impurities such as fluorine.

[0050] Step (i), which is carried out using a carbon-based material, such as carbon, as a reducing agent, comprises heating the lithium-containing transition metal oxide material to a temperature in the range of 200 to 900°C, preferably 300 to 850°C, more preferably 500 to 850°C.

[0051] According to this embodiment, the atmosphere used to carry out the reduction is either oxygen-free or contains up to 20% by volume of oxygen, the remainder being a non-oxidizing gas, preferably nitrogen, argon, water vapor, carbon monoxide, carbon dioxide, or a mixture of at least two of these gases. Preferred non-oxidizing gases are nitrogen and carbon monoxide, and mixtures of nitrogen and carbon monoxide. In a preferred embodiment, step (i) of the process is carried out under air or diluted air, for example, in an atmosphere containing 1 to 20% by volume, preferably 1 to 10% by volume (normal conditions), of oxygen, if present, the remainder being a non-oxidizing gas. In this embodiment of the invention, step (i) has a duration in the range of 10 minutes to 30 hours, preferably 20 minutes to 8 hours, more preferably 30 minutes to 4 hours. The duration of step (i), preferably in the presence of carbon, lasting 20 to 120 minutes, especially 30 to 120 minutes, is of particular technical interest.

[0052] After the heat treatment, the material is transferred from the oven to a cooling unit. Here, the material is cooled, preferably to a temperature below 100°C. Cooling can be carried out under ambient conditions, for example, by storing the hot material in a chamber or container, or in a rotary tube, which may be the last unheated or cooled part of a rotary kiln where the heat treatment is carried out and heat can be transferred to the environment. Preferably, the hot material can be cooled and conveyed by a cooling conveying screw. More rapid cooling can be achieved by introducing a gas, which can be fed to a heat exchanger after passing through the hot material bed. Such gas cooling can be designed as a fixed bed, a moving bed, or a fluidized bed. The gas used is preferably an inert gas such as nitrogen, argon, or carbon dioxide. Preferably, a reducing gas can be used at the beginning of the cooling period, when the material is still at a temperature close to the oven temperature, for reduction. Subsequently, at lower temperatures, the gas composition can be changed to an inert gas, or even an oxygen-containing gas such as air, or a mixture of air and an inert gas.

[0053] Alternatively, the hot material can be quenched with a liquid to cool it under dry conditions in a gas atmosphere. Quenching can be done by spraying a cooling liquid onto the hot material, either in an amount such that the liquid evaporates and the material remains essentially dry (evaporative cooling), or in a larger amount such that a slurry of the material is formed. Liquid cooling is particularly preferred when the resulting cooled material or slurry can be used directly in step (b) of this invention. Thus, preferred quench liquids are sufficiently temperature-stable polar solvents, with water being most preferred. The liquid can be pumped through a heat exchanger and returned to the cooling vessel for recycling.

[0054] In one embodiment of the present invention, the reduction conditions, with respect to hydrogen and / or carbon / oxygen concentration, and the temperature and duration of step (i) are selected so that at least a portion of the lithium-containing transition metal oxide material contains paramagnetic, antiferromagnetic, ferromagnetic, and / or ferrimagnetic components. The formation of ferromagnetic or ferrimagnetic components resulting from at least partial reduction of the lithium-containing transition metal material is preferred. The degree of reduction can vary within a range of 1 to 100% relative to the nickel content of the lithium-containing transition metal material, but is preferably in the range of 80 to 100%.

[0055] Thus, the particulate material provided in step (a) contains a transition metal compound and / or transition metal, the transition metal being selected from the group consisting of Mn, Ni and / or Co, and further wherein at least a portion of the Ni and / or Co, if present, is in an oxidation state lower than +2, and at least a portion of the Mn, if present, is manganese(II) oxide, in which the nickel and / or cobalt is typically at least partially in a metallic ferromagnetic state.

[0056] The presence of phases in oxidation states lower than +2, such as Ni and / or Co, Mn in the form of manganese(II) oxide, and metallic nickel and / or cobalt, can be detected by XRD, as further described below.

[0057] The presence of lithium salts in the particulate material provided in step (a) is detected by standard methods described below: The lithium salts contained in the particulate material provided in step (a) typically include one or more salts of LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, lithium phosphate salts, mixed oxides of Li and one or more of Ni, Co, Mn, Fe, Al, Cu, and / or fluorides of Ni, Co, Mn, Fe, Al, Cu.

[0058] LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, and lithium phosphate typically account for 95% or more by weight of all lithium salts present. When the particulate material prepared in step (a) is derived from a lithium-ion battery or part thereof, LiF, Li2CO3, LiOH, and lithium aluminate are very often present. If present, a larger proportion of the fluoride, e.g., 50% or more by weight of the fluoride, is typically present as lithium fluoride. Since the fluoride salts present typically originate in part from the electrolyte salt and polymeric binder of the former battery, hydrogen fluoride is liberated during the preliminary steps of discharging or dismantling or drying the battery materials, and other fluoride salts, such as cobalt fluoride, resulting from the rapid reaction of hydrogen fluoride with the former cell or electrode materials may be present as well.

[0059] The particulate material prepared in step (a) is typically a battery material containing lithium and one or more transition metals, including nickel and / or cobalt, such as a lithium-ion battery or a part of a lithium-ion battery, particularly a cell material thereof. For step (a), the material is prepared in the form of a dry powder, a wet powder, or a suspension of particles in a liquid. The material typically has an average particle diameter (D50 according to ISO 13320 EN:2009-10) ranging from 1 μm to about 2 mm, particularly ranging from 1 μm to 1 mm. In a typical process, an upper size limit for the particles in the powder material is imposed by a sieving step performed before step (a) or even before step (i), e.g., using a sieve that allows particles up to 2 mm, particularly up to 1 mm, to pass through its mesh.

[0060] Typically, the lithium-containing transition metal oxide material is obtained after mechanically removing the casing, wiring, or circuitry, and therefore typically consists primarily of cell materials. For safety reasons, such lithium-ion batteries are fully discharged or electrically discharged at least 80% (preferably more than 90%, most preferably more than 95%), for example, by immersion in a dry conductive bath, such as metal strips, so that residual electrical energy can be recovered, but which would otherwise cause a short circuit that constitutes a fire and explosion hazard. Such lithium-ion batteries can be disassembled, drilled, crushed, for example, in a hammer mill, or crushed, for example, in an industrial shredder. Although not preferred, the batteries can also be discharged by immersing them in a conductive liquid, for example, an aqueous solution of a metal salt such as sodium sulfate. Crushing can also be carried out in a liquid, preferably water. This has the advantage of preventing dust formation and the creation of an ignitable atmosphere.

[0061] Before subjecting the material to preliminary step (i), it may be advantageous to at least partially remove the electrolyte, in particular the electrolyte comprising an organic solvent or a mixture of organic solvents, for example by drying at subatmospheric pressure, for example at a temperature in the range of 50 to 250° C. As mentioned above, the lithium-containing transition metal oxide material is preferably not exposed to high temperatures (in particular above 400° C.) under oxidizing conditions before being subjected to this step (a).

[0062] Nevertheless, in one embodiment of the present invention, a heat treatment under oxidizing conditions may be carried out before the reduction step (i). This treatment may be carried out in a temperature range of 250-900°C, preferably between 350°C and 800°C, for example 300-400°C. To achieve oxidizing conditions, air or an oxygen-containing gas may be introduced into the reactor. The oxidation treatment may be carried out in the presence of alkaline earth hydroxides or oxides. The reaction may also be carried out in the presence of water as steam, thus applying hydrothermal conditions.

[0063] In one embodiment of the present invention, the lithium-containing transition metal oxide material is derived from battery scrap. In a preferred embodiment of the present invention, the lithium-containing transition metal oxide material is derived from mechanically treated battery scrap, for example, battery scrap treated in a hammer mill or industrial shredder. This mechanical treatment can be carried out under dry or wet conditions, preferably in the presence of water.

[0064] In one embodiment of the present invention, step (a) is preceded by step (a1), which comprises, for example, removing carbon or organic polymers by a solid-solid separation method. Examples of such solid-solid separation methods are electrosorting, sieving, magnetic separation, flotation or other classification methods. Solid-solid separation can be carried out dry or in the presence of a suitable carrier medium, preferably water.

[0065] In one embodiment of the present invention, the mechanically treated battery scrap is ground prior to step (a). Such grinding is preferably carried out in a ball mill or an agitated ball mill. Milling can be carried out under wet or dry conditions, with dry conditions being preferred.

[0066] In one embodiment of the present invention, before step (a), the mechanically treated battery scrap is contacted with water and / or an organic solvent, followed by a solid-liquid separation step.

[0067] In one embodiment, the mechanically treated battery scrap is contacted with a basic or acidic solution to promote the release of the active material from the electrode foil, as described in WO 2018 / 192122.

[0068] In one embodiment of the present invention, prior to the heat treatment of step (i), the mechanically treated battery scrap is subjected to a solvent treatment to dissolve and separate the polymeric binder used to bind the lithium transition metal oxide to the current collector film. Suitable solvents are N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and N-ethylpyrrolidone, dimethyl sulfoxide, hexamethyl phoshoramide, tetramethylurea, trimethyl phosphate and triethyl phosphate, in pure form or as a mixture.

[0069] The solvent treatment can be carried out with one or more solvents in successive steps or in one step using a solvent capable of dissolving the electrolyte components and the binder polymer. The solvent is applied at a temperature ranging from 10°C to 200°C. In particular, dissolution of the polymer may require elevated temperatures ranging from 50°C to 200°C, preferably between 100°C and 150°C. The upper temperature limit is usually limited by the boiling point of the solvent, unless pressures higher than 1 bar are applied.

[0070] In one embodiment, the cleaning of mechanically processed battery scrap is carried out with an aprotic solvent under the absence of moisture, for example, under a dry gas such as dry air or dry nitrogen.

[0071] In typical embodiments of the present invention, the lithium-containing transition metal oxide material includes battery scrap materials, parts of lithium-ion batteries or materials from parts, off-specification materials including pure electrode materials, or mixtures of such materials. However, the lithium-containing transition metal oxide material preferably contains, when applicable, nickel compounds, such as nickel / cobalt components, or compounds other than nickel / cobalt / manganese or nickel / cobalt / aluminum compounds, within the range of 0.1 to 80% by weight, and in extreme cases, valuable materials are in minor components. Examples of such components are carbon in an electrically conductive form, also referred to hereinafter as conductive carbon, for example, graphite, soot, and graphene. Further examples of impurities are copper and its compounds, aluminum and aluminum compounds, such as alumina, iron and iron compounds, zinc and zinc compounds, silicon and silicon compounds, for example, silica and silicon oxide SiO y [zero < y ≦ 2], tin, silicon-tin alloys, and organic polymers, such as polyethylene, polypropylene, and fluorinated polymers, such as polyvinylidene fluoride, tetrafluoroethylene polymers, etc. Further impurities are fluorine compounds, such as inorganic fluorides, and phosphorus compounds that may be derived from liquid electrolytes, such as widely used LiPF6 and impurities in the products derived from the hydrolysis of LiPF6. The battery scrap serving as the starting material for the method of the present invention may be derived from multiple sources, and thus, in the majority of embodiments, the lithium-containing transition metal oxide material contains, when applicable, nickel / cobalt compounds, or compounds other than nickel / cobalt / manganese or nickel / cobalt / aluminum components, and one such component is carbon in an electrically conductive form within the range of 2 to 65% by weight with respect to the entire lithium-containing transition metal oxide material.

[0072] In typical embodiments of the present invention, the lithium-containing transition metal oxide material contains one or more of the following additional components or impurities: i) copper, as metal or in the form of one or more of its compounds, in the range of 20 ppm by weight to 10% by weight, in particular 20 ppm by weight to 3% by weight, ii) aluminum in the form of one or more of its compounds, as the metal, in the range of 100 ppm to 15% by weight; iii) iron in the form of one or more of the metal or alloys or compounds thereof, in the range of 100 ppm by weight to 5% by weight; iv) zinc in the form of one or more of the metal or alloys or compounds thereof, in the range of 20 ppm by weight to 2% by weight; v) Zirconium in the form of one or more of the metal or alloys or compounds thereof, in the range of 20 ppm by weight to 2% by weight; vi) fluorine, calculated as the sum of the organic fluorine bound to the polymer and the inorganic fluoride in one or more of the inorganic fluorides, in the range of 1% to 8% by weight, in particular 2% to 8% by weight, vii) phosphorus, which may appear in one or more inorganic compounds, in the range of 0.2% to 2% by weight; viii) Manganese in the form of one or more of the metal or compounds thereof in the range of 100 ppm to 15% by weight.

[0073] Examples of such embodiments include one or two of the above additional components, or additional components (i), (ii) and (iii); (i), (ii) and (iv); (i), (ii) and (v); (i), (ii) and (vi); (i), (ii) and (viii); (i), (iii) and (iv); (i), (iii) and (v); (i), (iii) and (vi); (i), (iii) and (vii); (i), (iii) and (viii); (i), (iv) and (v); (i), (iv) and (vi); (i), (iv) and (vii); (i), (iv) and (viii); (i), (v) and (vi); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (vii) and (viii); (i), (ii), (iii) and (iv); (i), (ii), (iii) and (v); (i), (ii), (iii) and (vi); (i), (ii), (iii) and (vii); (i), (ii), (iii) and (viii); (i), (ii), (iv) and (v); (i), (ii), (iv) and (vi); (i), (ii), (iv) and (vii); (i), (ii), (iv) and (viii); (i), (ii), (v) and (vi); (i), (ii), (v) and (vii); (i), (ii), (v) and (viii); (i), (ii), (vi) and (vii); (i), (ii), (vi) and (viii); (i), (ii), (vii) and (viii); (i), (iii), (iv) and (v); (i), (iii), (iv) and (vi); (i), (iii), (iv) and (vii); (i), (iii), (iv) and (viii); (i), (iii), (v) and (vi); (i), (iii), (v) and (vii); (i), (iii), (v) and (viii); (i), (iii), (vi) and (vii); (i), (iii), (vi) and (viii); (i), (iii), (vii) and (viii); (i), (iii), (vii) and (viii); (i), (iv), (v) and (vi); (i), (iv), (v) and (vii); (i), (iv), (v) and (viii);(i), (iv), (vi) and (vii); (i), (iv), (vi) and (viii); (i), (iv), (vii) and (viii); (i), (v), (vi) and (vii); (i), (v), (vi) and (viii); (i), (v), (vii) and (viii); (i), (vi), (vii) and (viii); (ii), (iii), (iv) and (v); (ii), (iii), (iv) and (vi); (ii), (iii), (iv) and (vii); (ii), (iii), (iv) and (viii); (ii), (iii), (v) and (vi); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (viii); (ii), (iii), (vi) and (vii); (ii), (iii), (vi) and (viii); (ii), (iii), (vii) and (viii); (ii), (iv), (v) and (vi); (ii), (iv), (v) and (vii); (ii), (iv), (v) and (viii); (ii), (iv), (vi) and (vii); (ii), (iv), (vi) and (viii); (ii), (iv), (vii) and (viii); (ii), (iv), (vii) and (viii); (ii), (v), (vi) and (vii); (ii), (v), (vii) and (viii); (ii), (vi), (vii) and (viii); (ii), (vi), (vii) and (viii); (iii), (iv), (v) and (vii); (iii), (iv), (v) and (vii); (iii), (iv), (v) and (viii); (iii), (iv), (vi) and (vii); (iii), (iv), (vi) and (viii); (iii), (iv), (vii) and (viii); (iii), (v), (vi) and (vii); (iii), (v), (vi) and (viii); (iii), (v), (vii) and (viii); (iii), (vi), (vii) and (viii); (iii), (vi), (vii) and (viii); (iv), (v), (vi) and (vii); (iv), (v), (vi) and (viii); (iv), (v), (vii) and (viii); (iv), (vi), (vii) and (viii); (iv), (vi), (vii) and (viii); (v), (vii) and (viii);(i), (ii), (iii), (iv) and (v); (i), (ii), (iii), (iv) and (vi); (i), (ii), (iii), (iv) and (vii); (i), (ii), (iii), (iv) and (viii); (i), (ii), (iii), (v) and (vi); (i), (ii), (iii), (v) and (vii); (i), (ii), (iii), (v) and (viii); (i), (ii), (iii), (vi) and (vii); (i), (ii), (iii), (vi) and (viii); (i), (ii), (iii), (vii) and (viii); (i), (ii), (iii), (vii) and (viii); (i), (ii), (iv), (v) and (vii); (i), (ii), (iv), (v) and (viii); (i), (ii), (iv), (vi) and (vii); (i), (ii), (iv), (vi) and (viii); (i), (ii), (iv), (vii) and (viii); (i), (ii), (v), (vi) and (vii); (i), (ii), (v), (vi) and (viii); (i), (ii), (v), (vii) and (viii); (i), (ii), (vi), (vii) and (viii); (i), (ii), (vi), (vii) and (viii); (i), (iii), (iv), (v) and (vi); (i), (iii), (iv), (v) and (vii); (i), (iii), (iv), (v) and (vii); (i), (iii), (iv), (v) and (vii); (i), (iii), (iv), (v) and (viii); (i), (iii), (iv), (vi) and (vii); (i), (iii), (iv), (vi) and (viii); (i), (iii), (iv), (vii) and (viii); (i), (iii), (v), (vi) and (vii); (i), (iii), (v), (vi) and (viii); (i), (iii), (vi), (vii) and (viii); (i), (iv), (v), (vi) and (vii); (i), (iv), (v), (vi) and (viii); (i), (iv), (v), (vii) and (viii); (i), (iv), (vi), (vii) and (viii); (i), (iv), (vi), (vii) and (viii); (i), (v), (vii) and (viii); (i), (v), (vii) and (viii); (ii), (iii), (iv), (v) and (vii);(ii), (iii), (iv), (v) and (viii); (ii), (iii), (iv), (vi) and (vii); (ii), (iii), (iv), (vi) and (viii); (ii), (iii), (iv), (vii) and (viii); (ii), (iii), (v), (vi) and (vii); (ii), (iii), (v), (vi) and (viii); (ii), (iii), (v), (vii) and (viii); (ii), (iii), (vi), (vii) and (viii); (ii), (iv), (v), (vi) and (vii); (ii), (iv), (v), (vi) and (viii); (ii), (iv), (v), (vii) and (viii); (ii), (iv), (vi), (vii) and (viii); (ii), (v), (vi), (vii) and (viii); (iii), (iv), (v), (vi) and (vii); (iii), (iv), (v), (vi) and (viii); (iii), (iv), (v), (vii) and (viii); (iii), (iv), (vi), (vii) and (viii); (iii), (v), (vi), (vii) and (viii); (iv), (v), (vi), (vii) and (viii); (i), (ii), (iii), (iv), (v) and (vi); (i), (ii), (iii), (iv), (v) and (vii); (i), (ii), (iii), (iv), (v) and (viii); (i), (ii), (iii), (iv), (vi) and (vii); (i), (ii), (iii), (iv), (vi) and (viii); (i), (ii), (iii), (iv), (vii) and (viii); (i), (ii), (iii), (v), (vi) and (vii); (i), (ii), (iii), (v), (vi) and (viii); (i), (ii), (iii), (v), (vii) and (viii); (i), (ii), (iii), (vi), (vii) and (viii); (i), (ii), (iv), (v), (vi) and (vii); (i), (ii), (iv), (v), (vi) and (viii); (i), (ii), (iv), (v), (vii) and (viii);(i), (ii), (iv), (vi), (vii) and (viii); (i), (ii), (v), (vi), (vii) and (viii); (i), (iii), (iv), (v), (vi) and (vii); (i), (iii), (iv), (v), (vi) and (viii); (i), (iii), (iv), (v), (vii) and (viii); (i), (iii), (iv), (vi), (vii) and (viii); (i), (iii), (v), (vi), (vii) and (viii); (ii), (iii), (iv), (v), (vi) and (vii); (ii), (iii), (iv), (v), (vi) and (viii); (ii), (iii), (iv), (v), (vii) and (viii); (ii), (iii), (iv), (vi), (vii) and (viii); (ii), (iii), (v), (vi), (vii) and (viii); (ii), (iv), (v), (vi), (vii) and (viii); (iii), (iv), (v), (vi), (vii) and (viii); (i), (ii), (iii), (iv), (v), (vi) and (vii); (i), (ii), (iii), (iv), (v), (vi) and (viii); (i), (ii), (iii), (iv), (v), (vii) and (viii); (i), (ii), (iii), (iv), (vi), (vii) and (viii); (i), (ii), (iii), (v), (vi), (vii), and (viii); (i), (ii), (iv), (v), (vi), (vii), and (viii); (i), (iii), (iv), (v), (vi), (vii), and (viii); (ii), (iii), (iv), (v), (vi), (vii), and (viii). Another example is a lithium-containing transition metal oxide material containing each of the above additional components.

[0074] Each of the percentages given above is by weight of the dry material (ie, the lithium-containing transition metal oxide material provided in this step (a)).

[0075] In embodiments of particular technical interest, the particulate material provided in step (a) contains only small amounts of calcium or no calcium at all. Such transition metal compounds and / or transition metal-containing particulate materials may further contain lithium salts and fluoride salts, and optionally may contain calcium, so long as the elemental ratio of calcium to fluorine is 1.7 or less or zero.

[0076] The lithium-containing transition metal oxide material typically contains nickel or cobalt, or both nickel and cobalt. Examples of lithium-containing transition metal oxide materials may be based on lithiated nickel cobalt manganese oxide ("NCM") or lithiated nickel cobalt aluminum oxide ("NCA"), or mixtures thereof.

[0077] Examples of layered nickel-cobalt-manganese oxides are those of the general formula Li 1+x (Ni a Co b Mn c M 1 d ) 1-x O2 compound, M 1 is selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Mo, V, and Fe, with further variables defined as follows: zero≦x≦0.2 0.1≦a≦0.95, zero≦b≦0.9, preferably 0.05 <b≦0.5、 zero ≤ c ≤ 0.6, Zero≦d≦0.1 and a+b+c+d=1.

[0078] In a preferred embodiment, in the compound according to general formula (I), Li (1+x) [Ni a Co b Mn c M 1 d ] (1-x) O2(I) M 1 is selected from Ca, Mg, Zr, Al, Ti and Ba; Further variables are defined as above.

[0079] Examples of lithiated nickel-cobalt aluminum oxides are those of the general formula Li[Ni h Co i Al j ]O 2+r Typical values ​​for r, h, i and j are: h is in the range of 0.8 to 0.95, i is in the range of 0.02 to 0.3, j is in the range of 0.01 to 0.10, r is in the range of zero to 0.4.

[0080] Li (1+x) [Ni 0.33 Co 0.33 Mn 0.33 ] (1-x) O2, Li (1+x) [Ni 0.5 Co 0.2 Mn 0.3 ] (1-x) O2, Li (1+x) [Ni 0.6 Co 0.2 Mn 0.2 ] (1-x) O2, Li (1+x) [Ni 0.7 Co 0.2 Mn 0.1 ] (1-x) O2, Li (1+x) [Ni 0.8 Co 0.1 Mn 0.1 ] (1-x) O2 (where x is as defined above), and Li[Ni 0.85 Co 0.13 Al 0.02 ]O2 is particularly preferred.

[0081] The lithium-containing transition metal oxide material may have a regular shape, but usually has an irregular shape. However, it is preferable to remove as much of the light parts as possible, such as organic plastic housing parts and aluminum or copper foil, for example, in a forced gas flow.

[0082] In one embodiment, the composition of the atmosphere is changed during step (i), which may be done before switching the atmosphere to a reducing atmosphere, such as a hydrogen-containing atmosphere, for example, if volatile organic compounds are present in the feed that are removed in the inert atmosphere.

[0083] In one embodiment, an oxidizing atmosphere in the temperature range of 20-300°C is used in step (i) prior to reduction with a hydrogen-containing atmosphere. This embodiment allows some impurity components, i.e., organic components, to burn or dries the material (among other things, as further discussed above, temperatures of up to 250°C are utilized). A preferred oxidizing gas is oxygen or an oxygen-containing gas, such as air. Materials derived from spent lithium-ion battery cells, which contain lithium, transition metal oxides, and typically fluorine and / or phosphorus compounds, are preferably not subjected to oxidation above 300°C prior to carrying out the steps of the present method.

[0084] In one embodiment of the present invention, step (a) is preceded by step (a1), which comprises, for example, removing carbon or organic polymers by a dry solid-solid separation method. Examples of such dry solid-solid separation methods are electrosorting, sieving, magnetic separation or other classification methods. Here, step (a1) is introduced as an additional step.

[0085] In one embodiment of the present invention, the material provided in step (a) is ground prior to step (b) in order to de-agglomerate different solid particles from one another, if they are somewhat agglomerated, for example by residual binder polymer. The grinding can be carried out under dry or wet conditions. Preferably, the grinding is carried out in an aqueous medium which is also used in the subsequent step (b).

[0086] At the end of step (b), the pressure may be released if applicable. A solution of lithium salt is obtained from step (c) as a liquid, typically an aqueous solution containing LiOH.

[0087] Prior to this step (c), the solid residue is contained in a polar solvent, which may be an aqueous solution, to form a suspension. If the extraction of the Li compound is carried out in two or more steps as described above, the solid residue will be contained in the slurry of the second or last step, respectively.

[0088] The solid residue obtained in step (c) is recovered by solid-liquid separation step (c). This step may be a type of filtration or centrifugation, or settling and decantation, optionally followed by a washing step in which the respective polar solvent used as washing medium in step (b) is applied. The filtrate and washing liquid are usually combined before further work-up of the respective lithium salt. To recover such solid material, which contains fine particles, for example with an average diameter of 50 μm or less, a flocculating agent, for example polyacrylate, may be added.

[0089] The solid residue obtained by step (c) is characterized by a typical elemental composition resulting from the application of the preferred process conditions during step (b). Specifically, the solid residue is characterized by a composition typical of battery scrap material (Li, graphite, and at least one of Ni and Co, with Mn optionally present), but with a significantly higher (Ni + Co + Mn) to Li weight ratio. Because battery scrap material, particularly cathode active material, is characterized by a (Ni + Co + Mn):Li weight ratio between 5 and 12, the solid residue after step (c) has a lower Li content, and therefore a (Ni + Co + Mn):Li weight ratio between 13 and 100,000. Furthermore, the preferred process in step (b) is accompanied by a significant increase in calcium content, which, as mentioned above, is very low (0-0.5 wt%) in the initial particulate material prepared in step (a). The solid residue obtained by this preferred variant of step (c) is characterized by an elemental Ca weight content of between 2% and 50% by weight (based on the dry solid).

[0090] This solid residue obtainable by step (c) is a source of valuable materials useful in the production of new batteries, and steps for the isolation of such materials are described below.

[0091] The solid residue obtained by step (c) may subsequently be subjected to step (d1), a solid-solid separation to remove Ni and / or Co, if present. By carrying out step (d1), nickel is recovered as a nickel-containing solid.

[0092] When carrying out step (d1) of the present invention, it is preferable to include a wet solid-solid separation step. This solid-solid separation step serves to separate insoluble components such as carbon and polymers, or insoluble inorganic components such as metal or metal oxide particles, from the metal or metal oxide components of the lithium-containing transition metal oxide material. After the solid-solid separation of step (d1), a solid concentrate fraction is typically obtained, which contains a majority of Ni and, if applicable, Co in concentrated form. Such a solid-solid separation step can be carried out mechanically, by column or pneumatic means, or by combined flotation. In many embodiments, collector compounds are added to the slurry to render the target components hydrophobic. Typical collector compounds for carbon and polymer particles are hydrocarbons or fatty alcohols, which are introduced in amounts of 1 g to 50 kg per ton of solid residue obtained from step (c). Flotation can also be performed in the reverse sense, i.e., by converting originally hydrophilic components into strongly hydrophobic components using special collector materials, such as fatty alcohol sulfates or esterquats. Direct flotation using hydrocarbon collectors, such as mineral oil, kerosene, or diesel, is preferred. To improve the selectivity of flotation to carbon and polymer particles, inhibitors can be added to reduce the amount of metal and metal oxide components entrained in the froth phase. Agents that can be used include acids or bases to control the pH value within the range of 3 to 9. Ionic components, such as sodium silicate, that adsorb to metal or metal oxide surfaces, or bipolar components, such as amino acids, can also be used. To increase the efficiency of flotation, it can be advantageous to add carrier particles, such as polymer particles or carbonaceous particles, such as graphite or coal, that form agglomerates with hydrophobic target particles. Magnetic carrier particles can be used to form magnetic agglomerates that can be magnetically separated.When the target components are paramagnetic, antiferromagnetic, ferrimagnetic, or ferromagnetic, these components can also be separated by magnetic separation using high-intensity magnetic separators ("WHIMS"), medium-intensity magnetic separators ("MIMS"), or low-intensity magnetic separators ("LIMS"). Other solid-solid separation techniques use the density difference of the solid components, for example, the density difference between graphite and metals or metal oxides. These techniques include sink-float methods, which utilize a fluid of intermediate density to that of the solid components to be separated. Another technique in this class is heavy-liquid separation. Additional separation techniques based on density differences are spirals and hydrocyclones.

[0093] Combinations of at least two of the foregoing solid-solid separation techniques may also be utilized. These combinations may include roughing, scavenging, and cleaning steps typical of mineral processing flowsheets.

[0094] In a preferred embodiment, the solid-solid separation in step (d1) is magnetic separation.

[0095] In one embodiment of the present invention, the solid material obtained from step (c) is ground before step (d1) in order to free different solid particles from one another if they are somewhat agglomerated, for example by residual binder polymer. Such grinding is preferably carried out in a ball mill or stirred ball mill.

[0096] In one embodiment of the present invention, step (d1) is a wet solid-solid separation using an aqueous medium, preferably water, as the fluid. The weight ratio of the fluid medium to the solid material in such step (d1) is typically in the range of 1:1 to 99:1, preferably 2:1 to 9:1.

[0097] The wet solid-solid separation of step (d1) results in two slurries: one containing the target transition metal-containing solid material, and the other containing other components such as carbonaceous materials and polymers, and, if applicable, some inorganic compounds. By suitable selection and, if necessary, combination of solid-solid separation steps, at least 60% of the Ni and / or Co is obtained and concentrated in one fraction. Preferably, at least 80-99% of the Ni and, if present, Co is separated.

[0098] In one embodiment of the invention, the liquid phase of the slurry fed to step (d1) still contains dissolved lithium. In this case, one or the other or both slurries resulting from the solid-solid separation in step (d1) are advantageously subjected to solid-liquid separation to recover the lithium solution. The lithium solution may then be further processed in step (e).

[0099] For the extraction step (d), acid or ammonia leaching can be applied.

[0100] During step (d), the transition metal material is treated with a leaching agent, preferably an acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid, or a combination of at least two of the foregoing, for example a combination of nitric acid and hydrochloric acid. - inorganic acids, such as sulfuric acid, hydrochloric acid, nitric acid, organic acids, such as methanesulfonic acid, oxalic acid, citric acid, aspartic acid, malic acid, ascorbic acid or glycine, a base, such as ammonia, an amine, an aqueous solution of ammonia, ammonium carbonate, or a mixture of ammonia and carbon dioxide, or - Chelating agents, such as Na4EDTA, Na2H2EDTA, H4EDTA (in the following sections, these three chelating agents will be collectively referred to as simply EDTA) or dimethylglyoxime.

[0101] In one form, the leaching agent comprises an aqueous acid, such as an inorganic or organic aqueous acid. In another form, the leaching agent comprises a base, preferably ammonia or an amine. In another form, the leaching agent comprises a complexing agent, preferably a chelating agent. In another form, the leaching agent comprises an inorganic acid, an organic acid, a base, or a chelating agent.

[0102] The concentration of the leaching agent can vary within a wide range, for example, from 0.1 to 98% by weight, preferably between 10% and 80%. A preferred example of an aqueous acid is aqueous sulfuric acid, for example, with a concentration in the range of 10 to 98% by weight. Preferably, the aqueous acid has a pH value in the range of -1 to 2. The amount of acid is adjusted so as to maintain an excess of acid with respect to the transition metal. Preferably, the pH value of the solution obtained at the end of step (d) is in the range of -0.5 to 2.5. A preferred example of a base as a leaching agent is aqueous ammonia, preferably in the presence of carbonate or sulfate ions, with a molar ratio of NH3 to metal (Ni, Co) of 1:1 to 6:1, preferably 2:1 to 4:1. Suitable chelating agents, such as EDTA or dimethylglyoxime, are often applied in a molar ratio of 1:1 to 3:1.

[0103] Leaching may be carried out in the presence of an oxidizing agent. A preferred oxidizing agent is oxygen, either as a pure gas or in a mixture with an inert gas, such as nitrogen, or as air. Other oxidizing agents are oxidizing acids, such as nitric acid, or peroxides, such as hydrogen peroxide.

[0104] In one embodiment of the present invention, such step (d) can be carried out by dissolving the solid Ni concentrate obtained in step (c) or (d1) in an acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid.

[0105] In one embodiment of the present invention, such step (d) may be carried out by treating the solid Ni concentrate obtained in step (c) or (d1) with an aqueous solution of ammonium carbonate or ammonium bicarbonate, which may contain additional ammonia.

[0106] In one embodiment of the present invention, the Ni concentrate obtained from step (c) or (d1) is treated in step (d) with an acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid, and citric acid, or a combination of at least two of the foregoing, such as a combination of nitric acid and hydrochloric acid. In the case of aqueous acid, the concentration of the acid can vary within a wide range, for example, from 0.1 to 99% by weight, preferably between 10% and 96%. The amount of acid is adjusted so that an excess of acid is maintained. Preferably, the pH value of the solution obtained at the end of step (d) is in the range of -0.5 to 2.

[0107] A preferred example of the aqueous acid is aqueous sulfuric acid, for example, having a concentration in the range of 10 to 98% by weight. Aqueous sulfuric acid of 10% to 80% is particularly preferred.

[0108] The treatment according to step (d) can be carried out at a temperature in the range of 20 to 200° C., in particular 20 to 130° C. If temperatures above 100° C. are desired, step (d) is carried out at a pressure above 1 bar; otherwise, atmospheric pressure is preferred.

[0109] In one embodiment of the present invention, step (d) is carried out in a container protected against strong acids, such as molybdenum- and copper-rich steel alloys, nickel-based alloys, duplex stainless steel, or glass-lined or enamel- or titanium-coated steel. Further examples are polymer liners and containers made of acid-resistant polymers, such as polyethylene, e.g., HDPE and UHMPE, fluorinated polyethylene, perfluoroalkoxyalkane ("PFA"), polytetrafluoroethylene ("PTFE"), PVDF, and FEP. FEP stands for fluorinated ethylene propylene polymer, i.e., a copolymer of tetrafluoroethylene and hexafluoropropylene.

[0110] The slurry resulting from step (d) may be stirred, agitated, or subjected to a grinding process, such as in a ball mill or stirred ball mill, which often provides better access for the water or acid to the particulate transition metal material.

[0111] In one embodiment of the present invention, step (d) has a duration ranging from 10 minutes to 10 hours, preferably from 1 to 3 hours. For example, the reaction mixture in step (d) is stirred or pumped at a power of at least 0.1 W / L to achieve good mixing and avoid settling of insoluble components. Shearing can be further improved by utilizing baffles. All of these shearing devices must be sufficiently corrosion-resistant and may be manufactured from the same materials and coatings as those described for the vessel itself.

[0112] Step (d) may be carried out under an atmosphere of air or air diluted with N. However, it is preferred to carry out step (d) under an inert atmosphere, such as nitrogen or a noble gas, such as Ar.

[0113] Treatment according to step (d) dissolves metal compounds, including impurities other than carbon and organic polymers, remaining after the LiOH leaching in step (b). In most embodiments, a slurry is obtained after performing step (d). Residual lithium and transition metals, such as, but not limited to, nickel, cobalt, copper, and, where applicable, manganese, are often in dissolved form, e.g., salt form, in the leachate.

[0114] In embodiments where a so-called oxidizing acid is used in step (d), it is preferred to add a reducing agent to remove unused oxidant. Examples of oxidizing acids are nitric acid and a combination of nitric acid and hydrochloric acid. In the context of the present invention, hydrochloric acid, sulfuric acid, and methanesulfonic acid are preferred examples of non-oxidizing acids.

[0115] In one embodiment, step (d) is carried out under an inert gas such as nitrogen or argon.

[0116] Depending on the concentration and amount of aqueous acid used in step (d), the liquid phase obtained in step (d) may have a transition metal concentration ranging from 1 to a maximum of 25% by weight, preferably 6 to 15% by weight. The transition metal concentration depends on the solubility of the salt corresponding to the acid used. Preferably, to ensure a high metal concentration in solution, step (d) is carried out so that the transition metal concentration of the main metal, e.g., Ni, and optionally Co and Mn, is slightly below the solubility limit of the least soluble salt.

[0117] An optional step that may be performed after step (d) is the removal of undissolved solids, such as carbonaceous materials, and polymers originating from the battery housing. This step may be performed by filtration, centrifugation, or sedimentation and decantation, with or without the addition of a flocculant. The resulting solid residue may be washed with water and further processed, for example, by the solid-solid separation methods described above, to separate the carbonaceous and polymeric components.

[0118] In one embodiment of the present invention, step (d) and the removal of undissolved solids is carried out continuously in a continuous operation mode.

[0119] By dissolving the Ni concentrate in step (d) in the subsequent step (f1), the pH value of the above slurry or solution can be adjusted to 2.5 to 8, preferably 5.5 to 7.5, and even more preferably 6 to 7. The pH value can be determined by conventional means, such as potentiometric titration, and refers to the pH value of the continuous liquid phase at 20°C. The pH value can be adjusted by dilution with water or by adding a base, or a combination thereof. Examples of suitable bases are ammonia and alkali metal hydroxides, such as LiOH, NaOH, or KOH, in solid form, e.g., as pellets, or preferably as an aqueous solution. Combinations of at least two of the foregoing, such as ammonia and aqueous caustic soda, are also possible.

[0120] Preferably, optional step (f2) comprises removing the residual precipitate of carbonates, oxides, phosphates, hydroxides, or oxyhydroxides of Al, Cu, Fe, Zr, or Zn, or a combination of at least two of the foregoing, formed in optional step (f1). The precipitate may be formed during the adjustment of the pH value. The phosphate may be a stoichiometric or basic phosphate. Without wishing to be bound by any theory, the phosphate may be generated during the hydrolysis of hexafluorophosphoric acid or its decomposition products formed during the pretreatment of the particulate material prepared in step (a). The precipitate may be removed by filtration, centrifugation, or sedimentation. Preferred filters are belt filters, filter presses, suction filters, and crossflow filters. Filter aids and / or flocculants may be added to improve solid-liquid separation.

[0121] In a preferred embodiment of the present invention, step (f2) optionally comprises step (f3), which comprises treating the solution obtained after step (f1) or step (f2) with metallic nickel, metallic cobalt or metallic manganese, or any combination of at least two of the foregoing.

[0122] In optional step (f3), the solution obtained after step (f2) is contacted with metallic nickel, cobalt or manganese, or a combination of at least two of the foregoing, for example in a column. In such embodiments, it is advantageous to provide a column packed with metallic nickel, cobalt or manganese, or a combination of at least two of the foregoing, in agglomerated or granular form, for example as a fixed bed, and to allow the solution stream to flow through such a column.

[0123] In one embodiment of the present invention, step (f3) is carried out at atmospheric pressure.

[0124] In one embodiment of the present invention, step (f3) has a duration ranging from 30 minutes to 5 hours, which corresponds to the average residence time if step (f3) is carried out in a column.

[0125] In one embodiment of the present invention, step (f3) is carried out at a pH value ranging from 1 to 6, preferably at a pH of from 2 to 5. The lower the pH value in step (f3), the more the metal selected from Ni, Co and Mn dissolves under hydrogen formation.

[0126] Step (f3) is particularly useful for removing traces of copper. By carrying out step (f3), no new impurities are introduced into the transition metal solution, which would require additional purification steps. Even if the metallic nickel, cobalt, or manganese contains traces of copper, these will not dissolve.

[0127] The separation of copper in step (f3) may be carried out by electrolysis, preferably using an electrochemical filter cell, using a conductive particulate material, such as graphite contained in the black mass, as an electrode.

[0128] Alternatively, copper may be extracted by solvent extraction or ion exchange prior to precipitation of Al, Fe, Zr and / or Zn, which can be recovered as high-grade copper by electrowinning.

[0129] Individual metals may be recovered as pure metal salts from the mixed Ni-, Co-, and / or Mn-containing solution by procedures known in the art, such as precipitation as oxides, hydroxides, carbonates, or sulfides, solvent extraction, ion exchange, electrowinning, etc. These pure metal salts may be reintroduced into the synthesis of the active cathode material, for example, by steps (g1) and (g) below.

[0130] Optional step (g) is typically carried out following step (d) and optional steps (f1), (f2) and (f3) and involves precipitating the transition metal as a mixed hydroxide or mixed carbonate, preferably as a mixed hydroxide.

[0131] In a preferred embodiment of the present invention, step (g) is carried out by adding ammonia or an organic amine, such as dimethylamine or diethylamine, preferably ammonia, and at least one inorganic base, such as lithium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate or potassium bicarbonate, or a combination of at least two of the foregoing. Addition of ammonia and sodium hydroxide is preferred.

[0132] In one embodiment of the present invention, step (g) is carried out at a temperature in the range of 10 to 85°C, preferably 20 to 50°C. In one embodiment of the present invention, the concentration of the organic amine (or ammonia) is in the range of 0.05 to 1 mol / L, preferably 0.1 to 0.7 mol / L. The term "ammonia concentration" in this context includes the concentrations of ammonia and ammonium. Ni in the mother liquor 2+ and Co 2+ An amount of ammonia that results in a solubility of each of the above compounds of 1000 ppm or less, more preferably 500 ppm or less, is particularly preferred.

[0133] In one embodiment of the present invention, mixing is effected during step (g) of the process of the present invention, for example by means of a stirrer, rotor-stator mixer or ball mill. It is preferred to introduce a stirrer power of at least 1 W / l, preferably at least 3 W / l, more preferably at least 5 W / l into the reaction mixture. In one embodiment of the present invention, a stirrer power of up to 25 W / l can be introduced into the reaction mixture.

[0134] The optional step (g) of the method of the present invention may be carried out in the presence or absence of one or more reducing agents. Examples of suitable reducing agents include hydrazine, primary alcohols, such as, but not limited to, methanol or ethanol, ascorbic acid, glucose, and alkali metal sulfites. It is preferred not to use any reducing agent in step (g). The use of a reducing agent or an inert atmosphere, or a combination of both, is preferred when a large amount of manganese, e.g., at least 3 mol % relative to the transition metal moiety of the respective positive electrode active material, is present in the transition metal oxide material.

[0135] Step (g) of the method of the present invention may be carried out under an atmosphere of an inert gas such as, for example, nitrogen or argon or carbon dioxide.

[0136] In one embodiment of the present invention, step (g) is carried out at a pH value in the range of 9 to 13.5 for hydroxides, preferably 11 to 12.5, and at a pH value in the range of 7.5 to 8.5 for carbonates, the pH values ​​referring to the pH values ​​in the mother liquor determined at 23°C.

[0137] Step (g) may be carried out in a batch reactor or (preferably) continuously, for example in a continuous stirred tank reactor, or in a cascade of two or more, for example two or three, continuous stirred tank reactors.

[0138] Step (g) of the method of the present invention can be carried out under air, under an inert gas atmosphere, such as a noble gas or nitrogen atmosphere, or under a reducing atmosphere. An example of a reducing gas is SO2. It is preferred to operate under an inert gas atmosphere, especially nitrogen gas.

[0139] For purposes of further purification, the solid recovered in step (g) may be separated and dissolved in an acid, such as hydrochloric acid, or more preferably, sulfuric acid.

[0140] By practicing the method of the present invention, transition metals, such as nickel, and, where applicable, cobalt and / or manganese, can be recovered from battery waste materials or scrap from battery, cell, and cathode active material production, typically including nickel- and / or cobalt-containing cathode materials, in a form that is very easily convertible into cathode active material. In particular, the method of the present invention allows for the recovery of transition metals, such as nickel, and optionally cobalt and / or manganese, containing only tolerably trace amounts of impurities, such as copper, iron, and zinc, e.g., less than 10 ppm copper, and preferably even less, e.g., 1 to 5 ppm.

[0141] In one embodiment of the present invention, in an additional step (g1) prior to step (g), nickel, cobalt, and / or manganese salts are added to the recycled metal salt solution from step (d) or (f1), (f2), or (f3) to adjust the metal ratio to the desired mixed metal hydroxide precipitate composition, which can be used as a precursor material for the production of an active cathode material. During such precipitation, additional metal salts can be added, preferably as an aqueous solution of the anion of the acid used in step (d). An example of such a metal is aluminum, which can be added as aluminum sulfate. The mixed metal hydroxide precipitate can be separated from the liquid by solid-liquid separation and dried to obtain a dry mixed metal hydroxide precipitate having a water content of 10% by weight or less. This allows the direct production of a positive electrode active material precursor in the subsequent precipitation step (g).

[0142] In one embodiment of the present invention, the solid Ni and / or Co (especially Ni) concentrate obtained in step (c) or (d1) is treated with ammonium (bi)carbonate in aqueous solution at a concentration of 0.2-30% by weight, preferably 1-20% by weight. The slurry may be heated to a temperature of 30-150°C. Above the boiling point of the mixture, heating is carried out under pressure. Below the boiling point, the application of pressure is advantageous in order to maintain sufficient ammonia and carbon dioxide in the system.

[0143] The treatment with ammonium (bi)carbonate can be carried out under an inert atmosphere or in the presence of oxygen, e.g., under air. The leachate or solution may also contain additional ammonia and / or hydrogen peroxide.

[0144] The ammonium (bi)carbonate treatment dissolves Ni, and, where applicable, Co and / or Cu, as ammonium complexes. The concentration of the metal ammonium complexes in the leach liquid can be in the range of 0.2-30 wt% by metal, preferably 1-15 wt% by metal. The solution obtained by this treatment is subjected to solid-liquid separation, resulting in a solution containing mainly ammonium complexes of Ni, and, where applicable, Co and Cu, and a separated solid residue containing mainly other transition metals, i.e., Mn and Fe, where applicable.

[0145] The resulting solution can be heated and purged with carbon dioxide to remove ammonia. This results in the precipitation of first Ni carbonate, and, in longer treatments, advantageously at higher temperatures, also Co carbonate. This allows the separation of both metals. In one embodiment of the present invention, the Ni and Co carbonates are not separated from each other. The precipitated mixed Ni / Co carbonate is separated from the mother liquor and dissolved in sulfuric acid or another acid to obtain a solution of the corresponding Ni salt and, if applicable, Co salt. This solution may also contain small amounts of Cu salts, which can be removed by treatment with the metals Ni, Co, or Mn, as described above. Other impurities, such as Fe or Al, which may be present in low concentrations, can be removed by hydroxide or carbonate precipitation at pH values ​​of 2.5 to 8, as also described above.

[0146] Ni hydroxide and Co hydroxide can be coprecipitated from a solution of purified Ni salts and, if applicable, Co salts.

[0147] In one embodiment of the present invention, the solution is further processed to extract the Ni and Co salts separately, for example, by solution extraction. The pure metals can be recovered from the separated Ni and Co salts via electrochemical methods known in the art.

[0148] In one embodiment, the precipitation of the transition metals after steps (f1), (f2) and (f3) is carried out with hydrogen under elevated pressure. For this, the pH value of the solution is kept basic by adding ammonia and / or ammonium carbonate. This allows Ni, Co and Cu to precipitate as metals. Certain catalysts known in the art may be added to improve this reaction.

[0149] In step (e), the lithium-containing solution resulting from any of the steps described above, such as step (c) and / or step (d1), may be treated to recover lithium in the form of a solid material as hydroxide or salt.

[0150] In one embodiment of the present invention, the Li salt, particularly LiOH, is recovered by evaporation (e1) of the water contained in the solution, which may be carried out in two or more successive steps (e2 and e3, for example) to produce the desired high purity Li salt.

[0151] First, the Li-containing solution from one of the above steps is concentrated to a point near the solubility limit of LiOH. This step involves the solid formation (e.g., crystallization) of impurities with lower solubility than LiOH, including, but not limited to, Ca(OH)2, CaF2, CaCO3, and LiF. These are separated by solid-liquid separation, e.g., filtration or centrifugation, or by a type of settling and decantation. Because the residual amount of solids is small, a depth filter is preferably applied. A combination of two solid-liquid separation steps, e.g., a hydrocyclone followed by a depth filter, is also possible. If LiF precipitates during this first concentration step (e2), it is preferable to resupply the solid material to step (b).

[0152] The filtrate obtained from the solid-liquid separation after one of the concentration steps, i.e., the concentrated LiOH solution, is then used in the next evaporation step (e3). High-quality LiOH can be obtained by evaporating the remaining water and forming a LiOH solid. In the case of crystallization, the crystals are again separated from the remaining mother liquor by solid-liquid separation and optionally washed. Multiple crystallization steps followed by washing and solid-liquid separation are possible to concentrate impurities. Any mother liquor obtained from crystallization can be subjected to further evaporation and crystallization and / or recycled by introducing the mother liquor into step (b) or (e1), (e2) or (e3).

[0153] All of the above solidification steps are advantageously followed by drying of the solid. Drying either below 60° C. or at higher temperatures under humid conditions results in LiOH monohydrate, otherwise at least partially anhydrous LiOH is obtained.

[0154] In that case, according to the described step (e1), the filtrate obtained after step (c) is dried by total evaporation of a polar solvent, for example water, to obtain LiOH (anhydrous or monohydrate) of high purity (more than 98.5%), which contains, in addition to carbonaceous impurities (less than 0.35% by weight), an impurity spectrum characteristic of the process described above, for example less than 0.35% by weight of carbonaceous impurities.

[0155] For LiOH monohydrate, the characteristic impurities are calcium, fluorine, and sodium. Typical amounts of these in this LiOH monohydrate are as follows: Ca: 100wtppm~1.29wt% F: 0.1~1.29wt% Na: 0.1~1.29% by weight.

[0156] Furthermore, depending on the composition of the PM, significant amounts of zinc, aluminum, potassium, and chlorine may be present. In these cases, the characteristic amounts in the LiOH monohydrate obtained after step (e1) are within the following ranges: Zn: 20wtppm~1.29wt% Al: 50wtppm~1.29wt% K: 0.1~1.29wt% Cl: 0.1~1.29% by weight.

[0157] Depending on the drying conditions, anhydrous LiOH is obtained instead of the monohydrate, in which case the characteristic amounts of the above-mentioned impurities for the monohydrate are highly concentrated by a factor of 1.75 (corresponding to the molar weight of the monohydrate divided by the molar weight of the anhydrous) relative to 100% anhydrous LiOH.

[0158] All applicable steps, including steps (b), (c), (d1) and (e), are preferably carried out in an inert atmosphere, such as nitrogen, argon, or CO2-free air.

[0159] In one embodiment of the present invention, Li is recovered from the solution obtained in step (c) by precipitation as Li carbonate by addition of sodium or ammonium carbonate or by carbonic acid formed by dissolution of carbon dioxide, preferably under pressure (step e5).

[0160] In one embodiment, this Li carbonate is redissolved by further adding CO to the solution, preferably under pressure, to form dissolved LiHCO (e6). Possible impurities can be separated using prior art purification techniques, such as solvent extraction, precipitation, and / or ion exchange. Optionally, after this purification, the Li carbonate can be obtained by increasing the temperature of the solution, which directly results in the precipitation of Li carbonate (e7). Subsequent solid-liquid separation can provide the pure Li carbonate.

[0161] In a preferred embodiment of the present invention, Li is recovered as LiOH.

[0162] The resulting solid Li salt and / or LiOH may be further purified by dissolution and recrystallization as known in the art. [Example]

[0163] Description of method Particle size distribution measurements, including determination of D50, are carried out according to ISO 13320 EN:2009-10.

[0164] Elemental analysis of lithium, calcium and manganese (performed to determine, inter alia, the Li, Ca, Mn content of the particulate material provided in step (a)); The reagents are Deionized water, hydrochloric acid (36%), K2CO3-Na2CO3 mixture (dry), Na2B4O7 (dry), hydrochloric acid 50% by volume (1:1 mixture of deionized water and hydrochloric acid (36%)). All reagents are PA grade.

[0165] Sample preparation For this step (a), 0.2-0.25 g of particulate material (typically obtained from waste lithium-ion batteries after performing the preliminary reduction step (i)) is weighed into a Pt crucible and subjected to K2CO3-Na2CO3 / Na2BO7 melt digestion. The sample is combusted in an unshielded flame and then completely ashed in a muffle furnace at 600 °C. The remaining ash is mixed with K2CO3-Na2CO3 / Na2BO7 (0.8 g / 0.2 g) and melted until a transparent melt is obtained. The cooled molten cake is dissolved in 30 mL of water and 12 mL of 50% by volume hydrochloric acid is added. The solution is filled up to the specified volume of 100 mL. This work-up is repeated three times independently, and a blank sample is also prepared for reference purposes.

[0166] measurement The Li, Ca, and Mn contents in the resulting solution were determined by inductively coupled plasma optical emission spectroscopy (ICP-OES). Instrument: ICP-OES Agilent 5100 SVDV; Wavelengths: Li 670.783 nm, Ca 396.847 nm, Mn 257.610 nm; Internal Standard: Sc 361.383 nm; Dilution Factor: Li 100, Ca 10, Mn 100; Calibration: External.

[0167] Elemental analysis of fluorine and fluoride is carried out according to the following standardized methods: DIN EN 14582:2016-12 for sample preparation (waste samples) for determination of total fluorine content; detection method is ion-selective electrode measurement; DIN 38405-D4-2:1985-07 (water samples; digestion of inorganic solids followed by acid-supported distillation and fluoride determination using an ion-selective electrode).

[0168] Other metal impurities and phosphorus are similarly determined by elemental analysis using ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy) or ICP-MS (Inductively Coupled Plasma Mass Spectroscopy). Total carbon is determined by a thermal conductivity detector after combustion.

[0169] The phase composition of the solid (including the identification of manganese(II) oxide and Ni and Co (typically metallic) in oxidation states lower than +2 in the particulate material prepared in step (a)) is determined by powder x-ray diffraction (PXRD), which is carried out as follows:

[0170] The sample is ground to a fine powder and packed into a sample holder.

[0171] It utilizes two devices, each using a separate radiation source.

[0172] (1) Measurements using Cu radiation: The equipment used is a Bruker D8 Advance Series 2 with an auto-sampling unit. Primary side: Cu anode, beam divergence angle aperture 0.1° by ASS; Secondary side: divergence beam aperture 8 mm, Ni 0.5 mm, Solar 4°, Lynx-Eye (3° aperture).

[0173] (2) Measurements using Mo radiation: The equipment used is a Bruker D8 Discover A25 with an autosampling unit. Primary side: Mo anode with Johansson monochromator (Mo-K-Alpha 1), axis Solar 2.5°; Secondary side: ASS, Solar 2.5°, Lynx-Eye XE detector (3.77° aperture).

[0174] References are used to identify matches with the obtained reflection pattern. All relevant phases are well known in the literature, and the following references are consulted and used to calculate the theoretical diffraction pattern (see position and intensity of reflections in Table 1 below): a) Co x Ni 1-x : space group Fm-3m; x=0.5: Taylor et al., J. Inst. Met. (1950) 77, 585-594. x=0: Buschow et al.; J. Magn. Magn. Mater. 1983, 38, 1-22. b) Co; space group P63 / mmc; Buschow et al.; J. Magn. Magn. Mater. 1983, 38, 1-22. c) Li2CO3, space group C2 / c; J. Alloys Compd. (2011), 509, 7915-7921 d) LiAlO2, space group R-3m; Marezio et al., J. Chem. Phys. (1966) 44, 3143-3145. e) MnO, space group Fm-3m, Locmelis et al., Z. Anorg. Allg. Chem. 1999, 625, 1573.

[0175] [Table 1]

[0176] If characteristic reflections overlap with those of different crystalline phases (especially graphite, which makes up the largest proportion of the sample), additional measurements are performed using an alternative radiation source (e.g., Mo K alpha instead of Cu K alpha).

[0177] Abbreviations In the context of the present invention, normal pressure means 1 atm or 1013 mbar. "Normal conditions" means normal pressure and 20°C. Nl stands for normal liter, i.e. liter at normal conditions (1 atm, 20°C). PFA stands for polyfluoroalkoxy polymer.

[0178] Percentages refer to % by weight unless specifically defined otherwise. The expressions % by weight and wt% may be used interchangeably. Whenever mentioned, the terms "room temperature" and "ambient temperature" refer to a temperature between about 18°C ​​and 25°C. XRD refers to powder x-ray testing (radiation as indicated, typically 154 pm Cu k-alpha 1 radiation or 71 pm Mo k-alpha 1 radiation).

[0179] The present invention is further illustrated by the following examples.

[0180] [Example 1] Preparation of reduced mass from waste lithium-ion batteries Approximately 1 ton of mechanically processed battery scrap containing spent cathode active material, containing nickel, cobalt, and manganese, organic carbon in the form of graphite and soot, and residual electrolyte, as well as additional impurities including, among others, fluorine compounds, phosphorus, and calcium, is treated to obtain reduced mass by the method described in Jia Li et al., Journal of Hazardous Materials 302 (2016) 97-104. The atmosphere in the roasting system is air, and oxygen reacts with the carbon in the battery scrap to form carbon monoxide, and the treatment temperature is 800°C.

[0181] After reacting and cooling to ambient temperature, the heat-treated material is recovered from the furnace and mechanically processed to obtain particulate material that is analyzed by X-ray powder diffraction (Figures 1 and 2: Mo Ka radiation, Figures 3 and 4: Cu Ka radiation), elemental analysis (Table 2) and particle size distribution (Table 3).

[0182] The lithium content is 3.6% by weight and serves as a reference for all further leaching examples (see below). The fluorine is mainly expressed as inorganic fluoride (88%). The particle size is well below 1 mm, with a D50 determined to be 17.36 μm.

[0183] Comparing the obtained XRD patterns with the calculated reference patterns for Ni (CoxNi1-x, x = 0-0.6, which is identical), Co, Li2CO3, and LiAlO2 (see reference patterns in Table 1), it can be concluded that Ni exists exclusively as a metallic phase, either as pure Ni or as an alloy in combination with Co. For clarity, this result is confirmed by applying two different radiation sources. The presence of metallic nickel is supported by the qualitative observation that the entire sample exhibits typical ferromagnetic behavior when contacted with a permanent magnetic material. As lithium salts, Li2CO3 and LiAlO2 are unambiguously identified by their characteristic diffraction patterns.

[0184] The composition of the obtained black powder (PM) is shown in Table 2.

[0185] [Table 2]

[0186] [Table 3]

[0187] [Example 2] Leaching with Ca(OH)2 A 5 g quantity of the above-mentioned reduced battery scrap material (obtained as shown in Example 1) is charged into a PFA flask and mixed with 5, 1.5, 1.0, and 0.5 g of solid Ca(OH), respectively. 200 g of water is added with stirring, and the whole mixture is refluxed for 4 hours.

[0188] After 4 hours, the solids are filtered off and a filtrate sample is taken and analyzed for Li, F, carbonate, OH and Ca. The results are summarized in Table 4 below.

[0189] [Table 4]

[0190] Example 2a Leaching with Ca(OH)2, adding solid to liquid Example 2 is repeated, except that 5 g of the black powder obtained as shown in Example 1 and the specified amount of solid Ca(OH) are simultaneously added to 200 g of water with stirring. The results are similar to those reported in Table 4.

[0191] [Example 3] More solids 10, 20, and 30 g amounts of particulate material (PM) described in Example 1 were respectively loaded into PFA flasks and mixed with solid Ca(OH) at a fixed weight ratio of PM:Ca(OH) = 3.3:1. Each sample was further treated with 200 g of water following the procedure in Example 2, except that it was refluxed for 6 hours. The results are shown in Table 5.

[0192] Based on these results, we conclude that the efficiency of the present leaching process is not affected by the PM solids content.

[0193] [Table 5]

[0194] [Example 4] Parameter Variation Following the procedure of Example 2a, solid Ca(OH)2 and the particulate material (PM) described in Example 1 are added to 836.8 g of preheated water in a baffled glass reactor with stirring (three-stage crossbeam stirrer, 60 mm diameter). After continuing stirring at constant temperature for the period (t) indicated in Table 6, the solids are filtered off and a filtrate sample is analyzed. The amount of Ca(OH)2 and PM, temperature, stirring parameters, and analytical results (% = g found in 100 g of filtrate) are also summarized in Table 6.

[0195] [Table 6]

[0196] [Example 5] Solid LiOH from leached lithium filtrate The filtrate obtained from the process according to Example 2 is further treated by step (e1) above to obtain solid LiOH as monohydrate: 1 L of the filtrate containing 0.21 wt. % lithium is concentrated by evaporation (40 °C, 42 mbar) and finally dried at 40 °C and under a constant flow of nitrogen for 24 hours. Figure 5 shows the obtained LiOH monohydrate containing trace amounts of the impurity Li2CO3, due to contact with air during almost all process steps. Elemental analysis reveals carbonaceous impurities followed by F, Na, Ca, K as the main impurities (more than 200 ppm), and Al and Zn as trace impurities (less than 200 ppm).

[0197] [Example 6] Preparation of reduced mass from waste lithium-ion batteries (step a) Approximately 100 tonnes of mechanically treated and sieved battery scrap containing spent cathode active material containing nickel, cobalt and manganese, organic carbon in the form of graphite and soot, as well as residual electrolyte and additional impurities including, among others, fluorine compounds, phosphorus and calcium, is processed to obtain a reduced mass. The composition of this initial material is shown in Table 7. Reduction is carried out in a rotary kiln at 450°C in a 100% hydrogen atmosphere. A residence time of 60 minutes is achieved by adjusting the kiln angle and rotation speed. After reaction and cooling to ambient temperature in an inert atmosphere, the heat-treated particulate material is analyzed by x-ray powder diffraction (results similar to those shown in Figures 1-4), elemental analysis (Table 7), and particle size distribution (Table 8).

[0198] The lithium content is 3.0 wt.% and serves as a reference for all further leaching examples (see below). Fluorine is expressed as inorganic fluoride. Particle size is well below 1 mm, with a D50 determined to be 17 μm.

[0199] Comparing the obtained XRD pattern with calculated reference patterns for Ni (CoxNi1-x, x = 0-0.6, which is identical), Co, and Li2CO3, it can be concluded that Ni exists exclusively as a metallic phase, either as pure Ni or as an alloy in combination with Co. The presence of metallic nickel is supported by the qualitative observation that, when the entire sample is brought into contact with a permanent magnetic material, it exhibits typical ferromagnetic behavior. Li2CO3 is unambiguously identified as the lithium salt by its characteristic diffraction pattern. The composition of the resulting black powder (PM) is shown in Table 7 (right column).

[0200] [Table 7]

[0201] [Table 8]

[0202] [Example 7] Leaching with Ca(OH)2 (steps b and c) A 30 g quantity of the above-mentioned reduced battery scrap material (obtained as shown in Example 6) is charged into a PFA flask and mixed with 30 g of solid Ca(OH). 200 g of water is added with stirring and the whole mixture is refluxed for 6 hours.

[0203] After 6 hours, the solids are filtered off and washed with water. The filtrate (224.34 g) and the dried (12 hours, 90° C.) filter cake (37.82 g) are analyzed. The lithium content of the filtrate is determined to be 0.30 g / 100 g. The results of the filter cake analysis are shown in Table 9. The lithium recovery (amount of lithium in the liquid phase compared to the amount of lithium in the liquid + solid phases) is 77%.

[0204] [Table 9]

[0205] [Example 8] Acidic leaching of the solid residue obtained in Example 7 (step d) 20 g of the solid obtained after solid-liquid separation in step (c) is suspended in 36 g of water and heated to 45°C. After reaching this temperature, air is continuously bubbled through the mixture (10 L / h) and the administration of 44 g of sulfuric acid (50%) begins. Once the entire amount of acid has been administered, the mixture is kept at 45°C for another hour and then heated to 80°C for 4 hours. The mixture is then cooled and the solid is filtered off. The filter cake is washed three times and then dried (12 hours at 90°C). Table 10 shows the fractions obtained and the corresponding elemental analyses, demonstrating that all elements except Al were recovered in greater than 90% yield by acid leaching with sulfuric acid in the presence of air. The yield is calculated as the ratio of the amount in the liquid phase to the amount in the liquid phase plus the solid phase, respectively.

[0206] [Table 10]

[0207] [Example 9] Acidic leaching of the solid residue obtained in step (c). 5 g of the solid obtained after solid-liquid separation in step (c) is suspended in 50 g of water and heated to 45°C. After reaching this temperature, a mixture of sulfuric acid (50%, 6.90 g) and hydrogen peroxide (30%, 1.17 g) is added while maintaining the temperature constant. Once the total amount is added, the mixture is kept at 45°C for another hour and then heated at 80°C for 4 hours. The mixture is then cooled and the solid is filtered off. The filter cake is washed three times and then dried. Table 11 shows the fractions obtained and the corresponding elemental analysis.

[0208] [Table 11]

[0209] [Example 10] Each of the 24 post-leaching solid residues obtained in Example 4 (see Table 6) was treated with sulfuric acid (50%) to remove undissolved solids. The resulting solution was combined with NaOH to precipitate all transition metals from solution. The resulting precipitates are useful as precursors for battery cathode active materials. The present invention includes the following aspects. [Section 1] 1. A method for recovering one or more transition metals and lithium as Li salts from materials typically comprising waste lithium-ion batteries or parts thereof, comprising: (a) providing a particulate material containing a transition metal compound and / or transition metal, wherein the transition metal is selected from the group consisting of Ni and Co, and at least a portion of the Ni and / or Co is in an oxidation state lower than +2, and the particulate material further contains a lithium salt; (b) treating the material provided in step (a) with an alkaline earth hydroxide and a polar solvent, typically a protic solvent; (c) separating the solid residue containing the transition metal from the liquid, optionally followed by solid-solid separation to recover the transition metal, e.g., Ni; (d) treating the transition metal-containing solid, typically with a mineral acid or an ammoniacal solution, so as to dissolve at least a portion of the Ni and / or Co. A method comprising: [Section 2] Item 1. The method according to item 1, wherein the particulate material provided in step (a) is obtained from used lithium ion batteries, in particular cell materials thereof, and / or scrap materials obtained from the production of lithium ion batteries, or lithium ion positive electrode active materials, and is provided in the form of a dry powder, a wet powder, or a suspension of particles in a liquid. [Section 3] Item 3. The method of item 1 or 2, wherein the particulate material provided in step (a) comprises particles having an average particle diameter D50 in the range of 1 μm to 2 mm, as determined according to ISO 13320 EN:2009-10. [Section 4] 4. The method according to any one of items 1 to 3, wherein the transition metal compound and / or transition metal Ni and / or Co in an oxidation state lower than +2 contained in the particulate material prepared in step (a) comprises metallic Ni and / or Co, and the transition metal compound and / or transition metal contained in the particulate material prepared in step (a) is preferably present in an amount detectable by powder X-ray diffraction (Cu-k-alpha-1 radiation). [Section 5] 5. The method according to any one of items 1 to 4, wherein the lithium salt contained in the particulate material prepared in step (a) comprises one or more salts of LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, and lithium phosphate; or a mixed oxide of Li and one or more of Ni, Co, Mn, Fe, Al, and Cu. [Section 6] Step (b) is carried out in the presence of an alkaline earth hydroxide, preferably i) adding simultaneously a mixture comprising alkaline earth hydroxide and / or alkali oxide as a solid, or an alkaline earth hydroxide as a suspension or solution in a protic solvent, typically an aqueous liquid, and the particulate material provided in step (a) to a polar solvent, which is a protic solvent, preferably an aqueous liquid, e.g., water. By or ii) adding the particulate material provided in step (a) to a polar solvent, which is a protic solvent, preferably an aqueous liquid, e.g., water, to obtain a suspension, followed by adding an alkaline earth hydroxide and / or alkali oxide as a solid, or a mixture comprising an alkaline earth hydroxide as a suspension or solution in a protic solvent, e.g., an aqueous liquid. By or iii) adding alkaline earth hydroxides and / or alkali oxides, either as solids or as a suspension of the solids in a polar solvent, to an aqueous liquid, e.g., water, to obtain a mixture comprising alkaline earth hydroxides, typically as a suspension or solution in the aqueous liquid, and subsequently combining the mixture with the particulate material provided in step (a); By or iv) adding alkaline earth hydroxides and / or alkali oxides as solids to the particulate material provided in step (a) to obtain a mixture of solids, followed by the addition of a polar solvent, which is a protic solvent, preferably an aqueous liquid, e.g., water. By or v) adding the particulate material provided in step (a) to a polar solvent, preferably an aqueous liquid such as water, to obtain a suspension, followed by filtering to obtain a filtrate, followed by adding to the filtrate an alkaline earth hydroxide and / or alkali oxide as a solid, or a mixture comprising an alkaline earth hydroxide, typically as a suspension or solution in a polar solvent, preferably an aqueous liquid. The method according to any one of items 1 to 5, wherein the method is carried out by [Section 7] 7. The method according to any one of paragraphs 1 to 6, wherein the polar solvent in step (b) contains calcium hydroxide, which is added to the polar solvent as such or is formed in situ upon contact of calcium oxide with a polar solvent selected from a protic solvent, such as an aqueous liquid or water. [Section 8] 8. The method according to any one of items 1 to 7, wherein the particulate material provided in step (a) comprises material obtained from waste lithium ion batteries after a preliminary step (i) of heating to a temperature in the range of 80 to 900°C, in particular 200 to 800°C, under inert or reducing conditions, typically in the presence of carbon and / or a reducing gas selected from hydrogen and carbon monoxide, the preliminary step (i) preferably being carried out after discharging, dismantling and / or crushing the lithium ion batteries. [Section 9] 9. The method of any one of items 1 to 8, wherein the solid containing the transition metal is treated in step (d) with a mineral acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid, or a combination of at least two of the foregoing, typically in the presence of water, and optionally further in the presence of hydrogen peroxide. [Section 10] Item 10. The method according to Item 9, wherein in the preliminary step (i), the heating temperature is within a range of 350 to 500°C, particularly 350 to 450°C, and step (i) is carried out in the presence of 35% or more by volume of hydrogen; or in the preliminary step (i), the heating temperature is within a range of 500 to 850°C, particularly 600 to 800°C, and step (i) is carried out in the presence of carbon in an atmosphere containing up to 20% by volume of oxygen. [Section 11] 11. The method of any one of paragraphs 1 to 10, wherein the particulate material provided in step (a) is obtained from a lithium ion battery after mechanically removing any casing, wiring or circuitry and discharging, and the material has not been exposed to temperatures of 400°C or higher under oxidizing conditions prior to subjecting the material to step (a). [Section 12] 12. The method of any one of paragraphs 1 to 11, comprising the additional step of subjecting the solid obtained in step (c) to solid-solid separation, for example magnetic separation. [Section 13] 13. The method of any one of paragraphs 1 to 12, wherein the solid treated in step (d) further contains one or more of the elements copper, iron, and manganese. [Section 14] 12. The process of any one of paragraphs 1 to 11, comprising the additional step of recovering lithium as lithium hydroxide from the liquid obtained in step (c) by crystallization or recovering lithium as lithium carbonate after adding carbon dioxide to the liquid obtained in step (c) and isolating the lithium carbonate formed. [Section 15] Item 15. The method according to any one of items 1 to 14, wherein the transition metal obtained in step (d) is subjected to precipitation as a hydroxide, optionally after removing undesired impurity metals and / or adding a missing amount of metal as a corresponding salt, and optionally subsequently calcined, to achieve a desired metal composition of the positive electrode active material. [Section 16] Item 16. Use of the transition metal obtained from the material dissolved in step (d) according to any one of items 1 to 15 as a positive electrode active material precursor.

Claims

1. 1. A method for recovering one or more transition metals and lithium as Li salts from a material comprising waste lithium ion batteries or parts thereof, comprising: (a) providing a particulate material containing a transition metal compound and / or a transition metal, the transition metal being selected from the group consisting of Ni and Co, at least a portion of the Ni and / or Co being in an oxidation state lower than +2, the particulate material further comprising a lithium salt; (b) treating the material provided in step (a) with an alkaline earth hydroxide and a polar solvent; (c) separating the solid residue containing the transition metal from the liquid; and (d) treating the transition metal-containing solid with a mineral acid or an ammoniacal solution so as to dissolve at least a portion of the Ni and / or Co. Including, 1. A method according to claim 1, wherein the particulate material provided in step (a) is obtained from a lithium ion battery after mechanical removal of any casing, wiring or circuitry and discharging, and said material has not been exposed to temperatures of 400°C or greater under oxidizing conditions prior to subjecting it to step (a).

2. 2. The method of claim 1, wherein the particulate material provided in step (a) is obtained from used lithium ion batteries, and / or scrap material obtained from the production of lithium ion batteries, or lithium ion positive electrode active material, and is provided in the form of a dry powder, a wet powder, or a suspension of particles in a liquid.

3. 3. The method of claim 1 or 2, wherein the particulate material provided in step (a) comprises particles having a mean particle diameter D50 in the range of 1 μm to 2 mm, as detected according to ISO 13320 EN:2009-10.

4. 4. A method according to any one of claims 1 to 3, wherein the transition metal compounds and / or transition metals Ni and / or Co in an oxidation state lower than +2 contained in the particulate material prepared in step (a) comprise Ni and / or Co in the metallic state, and the transition metal compounds and / or transition metals contained in the particulate material prepared in step (a) are present in an amount detectable by powder x-ray diffraction (Cu-k-alpha-1 radiation).

5. 5. A method according to any one of claims 1 to 4, wherein the particulate material provided in step (a) contains lithium salts comprising one or more of the following salts: LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, lithium phosphate; mixed oxides of Li and one or more of Ni, Co, Mn, Fe, Al, Cu.

6. step (b) is carried out in the presence of an alkaline earth hydroxide; i) adding simultaneously to a polar solvent, which is a protic solvent, a mixture comprising an alkaline earth hydroxide and / or an alkali oxide as a solid, or an alkaline earth hydroxide as a suspension or solution in a protic solvent, and the particulate material provided in step (a); By or ii) adding the particulate material provided in step (a) to a polar solvent, which is a protic solvent, to obtain a suspension, followed by adding an alkaline earth hydroxide and / or an alkali oxide as a solid, or a mixture comprising an alkaline earth hydroxide as a suspension or solution in the protic solvent. By or iii) adding an alkaline earth hydroxide and / or an alkali oxide, either as a solid or as a suspension of the solid in a polar solvent, to the aqueous liquid to obtain a mixture comprising alkaline earth hydroxide, and subsequently combining said mixture with the particulate material provided in step (a); By or iv) adding an alkaline earth hydroxide and / or an alkali oxide, as a solid, to the particulate material provided in step (a) to obtain a mixture of solids, followed by adding a polar solvent, which is a protic solvent. By or v) adding the particulate material prepared in step (a) to a polar solvent, which is a protic solvent, to obtain a suspension, followed by filtering to obtain a filtrate, and then adding, as a solid, an alkaline earth hydroxide and / or an alkali oxide, or a mixture containing an alkaline earth hydroxide, to the filtrate. The method according to any one of claims 1 to 5, wherein the method is carried out by

7. 7. A method according to any one of claims 1 to 6, wherein the polar solvent in step (b) contains calcium hydroxide, which is added to the polar solvent as such or which is formed in situ upon contact of calcium oxide with a polar solvent selected from protic solvents.

8. 8. The method according to any one of claims 1 to 7, wherein the particulate material provided in step (a) comprises material obtained from waste lithium ion batteries after a preliminary step (i) of heating to a temperature in the range of 80-900°C under inert or reducing conditions, the preliminary step (i) being carried out after discharging, dismantling and / or crushing the lithium ion batteries.

9. 9. The method according to any one of claims 1 to 8, wherein the solid containing the transition metal is treated in step (d) with a mineral acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid, or a combination of at least two of the foregoing.

10. 10. The method of claim 9, wherein in the preliminary step (i), the heating temperature is in the range of 350-500°C and step (i) is carried out in the presence of at least 35% by volume of hydrogen, or wherein in the preliminary step (i), the heating temperature is in the range of 500-850°C and step (i) is carried out in the presence of carbon in an atmosphere containing up to 20% by volume of oxygen.

11. 11. The process according to any one of claims 1 to 10, comprising the additional step of subjecting the solid obtained in step (c) to solid-solid separation.

12. 12. The method of any one of claims 1 to 11, wherein the solid treated in step (d) further contains one or more of the elements copper, iron and manganese.

13. 11. The process according to any one of claims 1 to 10, comprising the additional step of recovering lithium as lithium hydroxide from the liquid obtained in step (c) by crystallization or as lithium carbonate after adding carbon dioxide to the liquid obtained in step (c) and isolating the lithium carbonate formed.

14. The method of claim 1, wherein the transition metals obtained in step (d) are subjected to precipitation as hydroxides to achieve a desired metal composition of the positive electrode active material.

Citation Information

Patent Citations

  • Battery recycling

    EP1589121A1

  • Lithium battery treating method

    JP2006004884A

  • Method for recovering lithium, cobalt and other metal

    JP2012112027A

  • Method for separating and recovering valuable material from used lithium ion battery

    JP2012229481A

  • Treatment method of lithium ion battery waste

    JP2015203131A